High-P-T experimental constraints on the genesis of post-collisional porphyry Cu-Au magmas: A case study from the southeastern Tibetan Plateau - Gong Liu; Xian-Wu Bi; Lei-Luo Xu; Wei Du; Lin-Bo Shang; Jing-Jing Zhu; Ming-Liang Huang; Rui Ma (Lithos, 2026)

L-Arginine effectively alleviates doxorubicin-induced cardiac dysfunction by inhibiting myocardial fibrosis - Mo-li Zhu; Rui Hao; Meng-yao Zhao; Pei-yao Liu; Hong-dou Zhang; Peng Li; Ya-ling Yin; Hui-jun Liu; Guang-qiu Ren; Jie Zhang; Jing Yang (Molecular Biology Reports, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Decoupling between chain extension and entanglement via branched structures for ultralow-power biaxially stretched polypropylene capacitor films - Qi Wu; Can Zhao; Enhui Liu; Xuan Wang; Jing Zhou; Rui Han; Min Nie (Chemical Engineering Journal, 2026)

Revealing spatiotemporal patterns of metro tidal ridership and their relationships with TOD features: A dual-sequence clustering and explainable machine learning approach - Rui An; Zhaomin Tong; Xiping Yang; Yaping Wang; Ying Jing; Yaolin Liu; Lin Luo; Jiayu Liu (Travel Behaviour and Society, 2026)

Biodiversity and paleoenvironmental reconstruction of the Jehol Biota in the Jiufengshan Formation of eastern Inner Mongolia, northeastern China - Yan Xue; Zhenhua Jing; Xiao Teng; Xin Zhang; Peihan Liu; Siyu Song; Rui Fang; Gang Li; Daran Zheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Research on the application of metal oxides in flue gas mercury removal enabled by machine learning - Yang Sun; Miao An; Rui He; Cui Jie; Jiaoyu Yang; Mi Liu; Zhiling Qian; Jing Yin; Yanxiao Cao; Hongcheng Ruan; Honghu Li (Journal of Environmental Chemical Engineering, 2026)

Prenatal exposure to outdoor artificial light at night and neonatal thyroid function: Identifying critical windows of susceptibility - Wanting Miao; Yanling Shu; Qing Fang; Gaojie Fan; Jing Peng; Li Zhang; Binghai Liu; Wenwen Guo; Lianyan Yan; Jiaoyan Li; Rui Chen; Xiaoning Lei; et al. (Environmental Pollution, 2026)

Multi-objective assessment of BIPV yield, complementarity, and economic feasibility - Rebecca Jing Yang; Chengyang Liu; Mathanky Sachchithananthan; Nilmini Weerasinghe; Yukun Zang; Helen Rose Wilson; Jonathan Leloux; Daniel Valencia-Caballero; Clarissa Debiazi Zomer; Malin Unger; Francesco Frontini; Hisashi Ishii; et al. (Energy and Buildings, 2026)

Efficient directional conversion of chemical energy contained in organic matter into cellular biomass energy induced by different terminal electron acceptors during activated sludge process - Rui Liu; Wen-Jing Li; Shao-Yang Liu; Jin-Song Guo; Fang Fang; You-Peng Chen; Peng Yan (Chemical Engineering Journal, 2026)

A review of atmospheric black carbon research progress in China - Qi Zhou; Shunyao Wang; Shujun Bie; Junjie Cai; Yingjun Chen; Yuan Cheng; Xiang Ding; Jianwei Gu; Jie Li; Weijun Li; Dantong Liu; Jiaying Liu; et al. (Atmospheric Environment, 2026)

Multi-pathway environmental and health impacts of volatile compound emissions from waste-to-energy plants in China - Guiying You; Hefan Liu; Xiaoya Dou; Rui Sun; Jing Li; Shaodong Xie (Atmospheric Environment, 2026)

Harnessing a MMP-sensitive fluorescent probe for in-situ and reversible monitoring MMP alteration in dual color based on aggregation/monomer mechanism - Mengmeng Wei; Yuxuan Zhang; Wuyou Qiang; Jiawei Liu; Yi Qian; Jing Xu; Xiaoyan Tang; Jiaojiao Liu; Shenqiang Wang; Tingwang Jiang; Xifeng Yang; Xuekun Hong; et al. (Analytica Chimica Acta, 2026)

Modulating local structural disorder in layered cathodes with alternating edge- and face-sharing octahedra for enhanced high-rate performance - Chengjun Fan; Xiaoxia Yang; Lingling Yao; Qin Wang; Xiao Ouyang; Leidang Zhou; Zhiwen Gao; Rui Jia; Xibang Chen; Jing Chen; Hao Liu; Bin Liao; et al. (Chemical Engineering Journal, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Prevalence and risk factors of bovine tuberculosis in dairy cattle, 2020–2025: A systematic review and meta-analysis of available literature - Qi Wang; Xiao-Nan Wang; Xiao-Qun Liu; Long-Ge Zhao; Zi-Tong Jing; Tian Tian; Jia-Ting Zhang; Yi-Xing Zhao; Jian-Ming Li; Nai-Chao Diao; Kun Shi; Rui Du (Preventive Veterinary Medicine, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Time-resolved structural remodeling and bioactivity changes of Lentinula edodes polysaccharides during fermentation by Limosilactobacillus fermentum CICC 21828 - Yue Liu; Saiqun Wang; Lu Liu; Zidan Zhao; Rui Cai; Jing Guo; Tianli Yue; Yahong Yuan; Zhouli Wang (Food Bioscience, 2026)

A novel AGTPBP1-ERK/MYLK network mediates pancreatic cancer progression - Zhe-yu Yang; Qian Zhang; Jing-rui Yang; Xiao-dong Zhang; Chang-le Liu; Jia-yu Huang; Rui Xiao; Jian-jun Ren (Tissue and Cell, 2026)

Optimization of magnetic field-assisted freezing via response surface methodology and its impact on blueberry freeze-thaw quality - Bowen Chen; Xinqun Zhou; Jing Sun; Rui Wang; Min Zhang; Ning Ji; Tingchao Liu; Bangdi Liu; Lihua Jiang (International Journal of Refrigeration, 2026)

Critical roles of CD4-1+ T cells and their secreted IL-21 in vaccine-induced humoral immunity in grass carp - Nan Zhang; Xun Liu; Rui Zhu; Wen-Jing Dong; Yan-Hui Huang; Yong-An Zhang; Xu-Jie Zhang (Fish & Shellfish Immunology, 2026)

Two new protoflavonoids from Polytrichum commune and their cytotoxicity against human gastric cancer cells - Jing-jing Dong; Dan-rui Han; Hao Cheng; Xu-liu Shi; Dong-Lai Ma; Jian-kun Yan; Xu-Hong Duan (Natural Product Research, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Seasonal and scale-dependent regulation of dissolved organic matter by anthropogenic activities in a karst river - Yuekai Ding; Rui Liu; Jing Zhang; Maofei Ni; Jie Liu; Weihua Yuan; Yan Dai; Yuankun Zhang (Journal of Environmental Management, 2026)

Characteristics of VOCs and sulfur-containing compounds: Environmental and health implications in odor complaint hotspots of Chengdu, China - Guiying You; Liqiu Huang; Hefan Liu; Xiaoya Dou; Rui Sun; Jiaxin Wei; Jing Li (Journal of Environmental Sciences, 2026)

Identification of transient receptor potential vanilloid 1-specific agonists from ginger polyphenols and analysis of their mechanism of action in ameliorating skeletal muscle insulin resistance - Lu Lu; Yifan Wang; Rui Liu; Beicheng Fang; Minjie Zhao; Fengqin Feng; Jing Wang (Food Bioscience, 2026)

Hybrid CFx/CrxOy as a high energy and power cathode for lithium primary batteries - Wen Liu; Sen Ma; Haijuan Pei; Rui Guo; Jing Liu; Yong Li; Jingying Xie (Chemical Engineering Journal, 2026)

Tailwater Treatment Using a Novel Coupled System of Microbial Electrolysis Cells Powered by Constructed Wetland-Microbial Fuel Cells - Jinhui Zhao; Lei Liu; Qingquan Liu; Tong Wu; Yanxia Wang; Jing Rui (Water, Air, & Soil Pollution, 2026)

Rhizosphere microbiome and soil health effects on ginseng growth performance and ginsenoside accumulation - Jing Fang; Rui Liu; Kemeng Zhang; Yingmei Sun; Yan Xue; Changbao Chen; Tao Zhang; Qinghe Zhang; Jia Chen (Plant and Soil, 2026)

Effects of dietary Portulaca oleracea L. aqueous extract on growth performance, intestinal health and intestinal microflora of common carp (Cyprinus carpio) - Jing-Tong Huang; Cong-Fu Liu; Yu-Shi Cai; Li-Fang Li; Hai-Tao Zhao; Yan-Ping Yang; Rui-Fang Wang (Animal Feed Science and Technology, 2026)

Duplex real-time qPCR assay targeting β-tubulin SNPs for detection of albendazole resistance in Haemonchus contortus - Xindi Chen; Lili Zhang; Tengyu Wang; Hao Zhang; Rui Wang; Jing Lu; Wa Gao; Wenlong Wang; Chunxia Liu (The Veterinary Journal, 2026)

Glucose stabilizes the KLF5 transcription factor to promote glycolysis and malignancy of basal-like breast cancer - Rui Liu; Yu Tang; Wenjing Liu; Chunli Zhou; Zhongmei Zhou; Wen Liu; Qiang Yu; Longlong Zhang; Jian Sun; Jing Peng; Yongchun Zhou; Dewei Jiang; et al. (Science Bulletin, 2026)

Experimental study on the wave mitigation characteristics of a grid-type flexible-membrane breakwater under regular waves - Chuan-Rui Li; Jing-Ping Wu; Ming-Liang Cai; Jun-Ao Kang; Chang-Zhe Chen; Hong Fan; Chen-Xia Liu; Shi-Yu Yang; Zi-Wen Xu (Ocean Engineering, 2026)

Comparative analysis of guide vane edge profiles in LPBF-manufactured elbows for enhanced flow performance - Mengyang Wang; Dingbo Li; Xiaochao Liu; Rui Nie; Zhenyu Wang; Jing Yao (Ocean Engineering, 2026)

Enhanced anti-hypoxia efficacy of morin via a ROS-responsive dextran-based nanodelivery system - Hang Gao; Nannan Jing; Yongkang Pan; Rui Li; Ting Wang; Xin Liu; Jiaqing Zhu; Jike Lu (Food Bioscience, 2026)

Effect of two double-stranded RNA viruses on the virulence of the phytopathogenic fungus Fusarium oxysporum - Jing Wang; Yunxia Ni; Xintao Liu; Hui Zhao; Xingbei Zhao; Rui Qiu; Siyuan Feng; Xiaoyuan Tian; Shouye Song; Shujun Li; Hongyan Liu (Archives of Virology, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

The Role of Metal Ions in Mitochondria: From Energy Metabolism to Cell Destiny - Chunlan Li; Hongpeng Liu; Qiuyue Mao; Jing Fu; Yu Yin; Lijuan Zhu; Kunrong Li; Rui Li; Pengyue Zhang (Biological Trace Element Research, 2026)

A Cu-based catalytic molecularly imprinted electrochemical sensor on paper for phthalylsulfacetamide detection in environmental water - Shuyan Miao; Jing Zhou; Zhen Xu; Yuting Wang; Rui Liu; Tian Gan (Journal of Environmental Chemical Engineering, 2026)

Enhancing Phytoremediation of Multi-Metal Contaminated Soil by Tagetes patula L. using Amycolatopsis tucumanensis KC 316 - Xiaoming Wang; Yajie Wu; Dejun Kong; Haotian Dong; Changyou Zhao; Murad Muhammad; Jing Zhang; Yuanchun Yang; Rui Liu; Shuai Wang; Aoli Zhang; Chunmei Lu; et al. (Journal of Environmental Sciences, 2026)

Energy input rate as a key switch: tuning product distribution and carbon structure in waste tire pyrolysis via conventional and microwave heating - Peng Liu; Shuxiao Wang; Jing Gu; Rui Shan; Yanzhi Sun; Junqing Pan; Haoran Yuan; Yong Chen (Fuel, 2026)

The mechanism of reducing the oil content of fried instant noodles by adding sugar alcohol: microstructure, surface properties and molecular structure - Rui He; Xiaomeng Ma; Ju Chen; Chengrong Zheng; Dingwu Zhang; Chong Liu; Jing Hong; Binghua Sun; Mei Liu; Jiaying Shang; Zipeng Liu; Xueling Zheng (Food Research International, 2026)

Accelerating Sugarcane Breeding with Machine Learning: A Concurrent Multi-trait Predictive Approach - Haichuan Fan; Jing Chao; Xiaoyan Liu; Pengcheng Ma; Guanghu Zhu; Ming Li; Rui Yan; Xinyi Li; Yan Jing; Fengbing Li; Ting Luo; Prakash Lakshmanan (Sugar Tech, 2026)
A large and highly polyploid genome, long breeding cycles, low narrow-sense heritability of yield and its components, and persisting yield stagnation continue to challenge sugarcane variety improvement through both conventional and molecular breedings. To address this, this study developed an efficient phenotype-based concurrent multi-trait prediction framework using artificial intelligence, leveraging 2700 parent combinations and their offspring field performance data from the Sugarcane Research Institute of Guangxi Academy of Agricultural Sciences. Five machine learning paradigms were selected based on data characteristics: tree-based models (GBDT, XGBoost) for structured tabular data and nonlinear trait interactions; attention-based tabular models (TabTransformer, TabNet) for subtle cross-trait dependencies; and an MLP as a baseline. All models were optimized via 80/20 stratified train–test split, class-weighted loss, and cross-validated grid search. GBDT achieved the best overall performance with a macro F 1 score of 0.7316, Hamming loss of 0.2052, and sample accuracy of 0.5630, excelling in predicting sucrose content, cane yield, and smut resistance. XGBoost performed comparably, while TabTransformer offered complementary advantages with a higher F 1 score (0.6829) on overall agronomic performance. These results indicate the potential of using artificial intelligence (AI), particularly machine learning (ML), to increase the predictive power and robustness through integrated AI approaches in the future. This phenotype-based framework shows the value of ML as an efficient decision support tool that can help breeders prioritize cross combinations and optimize resource use, thereby reducing reliance on extensive field trials. While the potential of AI in accelerating variety development is evident, its routine application in real-world commercial breeding requires validation.

Erzhi pills: a potential aging-modulating agent targeting immunosenescence in mice - Zhirui Fang; Wei Sun; Na Li; Tingting Shi; Xiuyun Ren; Rui Zhang; Yujing Zhang; Jing Chen; Qi Liu; Meng Wang; Lu Chen; Hong Wang (Biogerontology, 2026)

Spatial Distribution Characteristics of Secondary PM2.5 in Beijing-Tianjin-Hebei Region Based on Time Series Decomposition - Qing Yao; Jing Ding; Zi-rui Liu; Xu Yang; Ying-xiao Tang; Zi-yin Cai; Su-qin Han (Aerosol Science and Engineering, 2026)

Elucidating the pharmacological mechanism of Yangming-Kaixin-Yizhi formula in inhibiting neuronal ferroptosis via Nrf2 in Alzheimer’s disease: a study combining network pharmacology, transcriptomics, and experimental validation - Rui Xiong; Pan Liu; Lu Wang; Shipeng Zhang; Hengxu Liu; Cuiping Rong; Nurmuhammat Kehriman; Jianjun Wang; Jing Wang; Xiaodan Lai; Yong Tang (Metabolic Brain Disease, 2026)

Network pharmacology and animal experiments reveal the mechanism of action of hydroxysafflower yellow a against liver fibrosis - Qing Liu; Rui Wang; Zhenbo Li; Yihan Liu; Lei Wu; Jing Yang (South African Journal of Botany, 2026)

Broccoli plant elicitor peptide BoPep4 enhances plant salt tolerance by improving glucosinolate metabolism - Rui Li; Meihan Liu; Xiaoxue Hu; Jianing Li; Qiuying Pang; Xiufeng Yan; Jing Li; Wei Ji (Plant Science, 2026)

Multi-omics reveals that Sophora alopecuroides lysine decarboxylase (SaLDC)-mediated polyamine metabolism enhances salt tolerance and early flowering in Arabidopsis - Yongli Tian; Rui Wang; Jing Su; Wenjuan Li; Ping Liu; Chengke Luo; Jiaojiao Qian; Danting Zhang; Peifu Li; Bin Wang; Rong Yang; Tianli Ma; et al. (Plant Science, 2026)

Breaking the trade-off: Trichoderma effector Tahfb1 dual-targets growth and defense pathways via Hsp70L - Yaping Yin; Yuhang Fu; He Wu; Liping Feng; Lijuan He; Runmao Lin; Rui Wang; Zhengbin Tang; Baoping Zhu; Jumei Hou; Jing Zhao; Tong Liu (Pesticide Biochemistry and Physiology, 2026)

Turbulent up-flow hydrodynamic optimization enables high-rate anaerobic membrane bioreactor for refractory PTA wastewater treatment - Xinyu Jing; Yibo Sun; Lingtian Hu; Rui Deng; Zhaobin Liu; Xintao Wu; Yijing Gao; Danni Shi; Jiandong Wang; Guangyin Zhen; Jingjing Mai; Xueqin Lu (Journal of Water Process Engineering, 2026)

Construction and application of controlled-release preservation pads based on Zein/sodium caseinate-stabilized oregano essential oil Pickering emulsions - Liu Yang; Wenwen Chen; Xinyu Zhang; Rui Xiao; Xue Ding; Zhipeng Jing; Hongyuan Zhang (Food Hydrocolloids, 2026)

Prenatal air pollution exposure and postpartum glucose intolerance in women with gestational diabetes mellitus: Identifying susceptible windows - Gaojie Fan; Qing Liu; Li Zhang; Jing Peng; Li Wu; Qing Fang; Wenwen Guo; Binghai Liu; Lianyan Yan; Jiaoyan Li; Wanting Miao; Rui Chen; et al. (Environmental Research, 2026)

Deriving predicted no-effect concentrations for PFASs to protect threatened and endangered fish: A comparison of water- andtissue-residue-based toxicity data - Jiayu Wang; Xiaolei Wang; Qingyuan Cao; Rui Wang; Yuanpu Ji; Jing Zhang; Fengchang Wu; Zugen Liu; Xiaoli Zhao (Environmental Research, 2026)

The Multifaceted Potential of Fungi in Extraterrestrial Environments: Exploring Mushrooms in Space - Rui‐Meng Liu; Saowaluck Tibpromma; Wen‐Hua Lu; Nimesha M. Patabendige; Dong‐Qin Dai; Jing‐Ya Yang; Kalani K. Hapuarachchi; Samantha C. Karunarathna (New Zealand Journal of Botany, 2026)
Sustainable life support systems are essential for successful human space exploration beyond Earth. While soil fungi are potential candidates for exploitation in space, this review addresses contentious hypotheses, such as panspermia or putative Martian fungi, with scientific caution. The unique characteristics of mushrooms in extraterrestrial environments include their versatility, nutritional value, and tolerance of bioregenerative life support systems. Mushrooms are highly tolerant of extreme conditions, that is, microgravity and radiation‐intensive environments. They have the ability to degrade waste, produce edible biomass, and contribute to atmospheric control. The nutritional value of mushrooms, rich in proteins and vitamins, and their therapeutic, immunomodulatory, and antioxidant effects greatly benefit the health of astronauts. Space‐grown mushrooms can be engaged in improving the psychological condition and interpersonal relationships of astronauts. Even though there are challenges like microgravity and contamination in space mushroom cultivation, recent genetic and biotechnological approaches show promising solutions. This review highlights the motivational and critical role mushrooms play in sustaining human life in space, driving further research and commercializing cultivation activities.

Tracking the eyes to track decline: Global eye movement similarity as a novel neuropsychological marker of mild cognitive impairment - Zhan Wang; Hong-Zhou Xu; Fang Fang; Xue-Rui Peng; Ying-Chen Liu; Zhi-Jun Zhan; Jing Yu (GeroScience, 2026)

Plant protoberberine alkaloids: structural diversity, biosynthesis, synthesis, biological activity, structure-activity relationships and clinical applications of berberine - Weiqi Jiang; Wen Zhang; Chenxin Jing; Han Zhou; Zhi-Jun Zhang; Rui Wang; Ying-Qian Liu (Phytochemistry, 2026)

Grain-size controls on quartz OSL sensitivity in fluvial systems: insights from transport mechanisms in the upper Yellow River - Ya Liu; Song-Xi Du; Jia-Fu Zhang; Xue Rui; Yu-He Shen; Jia-Jing Wang; Qing-Hao Ma; Zheng-Hao Gu (Geomorphology, 2026)

A multi-stimuli-responsive supramolecular polymer from γ-Cyclodextrin and Viologen for dual-mode display and ammonia/amines sensing - Dong-Xue Xia; Chen-Yan Xu; Dan-Xuan Pan; Ming-Fu Ye; Rui-Lian Lin; Jing-Xin Liu (Chemical Engineering Journal, 2026)

Molecular dipole engineering enabled TiO2 electron transport layers for stable quantum-dot light-emitting diodes - Hang Liu; Pei-Li Gao; Bo Li; Hui Bao; Yin-Man Song; Meng-Wei Wang; Ting Ding; Jing Jiang; Rui-Feng Zheng; Feng-Jia Fan; Hai-Zheng Zhong; Kar-Wei Ng; et al. (Chemical Engineering Journal, 2026)

Plasma-ball milling assisted core-shell Si@SiOx/SiO2@C hybrid anode enabling highly stable Li-ion storage - Wen-Hua Shi; Zhi-Wen Yin; Zong-Bu Qin; Qing-Qing Yang; Rui-Qing Wang; Zi-Shuo Xia; Zhao-Dong Qiu; Jing Liu; Zhi-Yi Hu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Mitochondria to nucleus/nucleolus migration probe for in-situ and dual-color visualization of MMP alteration and monitoring apoptosis - Mengmeng Wei; Derong Xiang; Yuxuan Zhang; Wuyou Qiang; Jiawei Liu; Jing Xu; Xiaoyan Tang; Qijian Zhang; Zhida Han; Xifeng Yang; Rui Yang (Analytica Chimica Acta, 2026)

Brominated organic compounds in leachate across China: Occurrence and molecular variations - Jing Zheng; Ji-Tao Lv; Yue Sun; Qing-Yu Liu; Qiu-Rui Zhang; Zi-Meng Wang; Xiao-Song He (Water Research, 2026)

Gastrin releasing peptide receptor antagonism in the paraventricular nucleus exerts antihypertensive effects in 2K1C rats - Xiao-Min Wang; Jin-Jun Liu; Yi-Pu Wang; Chao Bai; Abdoulaye Issotina Zibrila; Wen-Jie Xia; Rui-Na Yang; Yu-Ming Kang; Xiao-Jing Yu (Toxicology and Applied Pharmacology, 2026)

Multi-omics analyses identify the modulators COX6A1 and NAL as regulators of silk cocoon formation in Plutella xylostella - Rui-Chang Niu; Qing-Hui Zeng; Wen-Jing Wang; Jia Hu; Tong-Xian Liu; Shi-Ze Zhang (Pesticide Biochemistry and Physiology, 2026)

Cumulative leaching behavior in sustainable vanadium extraction from V-slag using Ba-Slag - Hong-Rui Yue; Ya-Kun Zhao; He Yang; Xiang-Xin Xue; Jing Liu (Minerals Engineering, 2026)

Enhanced evapotranspiration prediction by incorporating plant stomatal-hydraulic co-regulation into hydrological model - Yong Liu; Tiesong Hu; Huandi Li; Xiang Zeng; Rui Zhu; Peiran Jing; Qifan Zhang; Xiang Li; Yanxuan Wang (Journal of Hydrology, 2026)

Land use alters dissolved organic matter in the three gorges reservoir area: Direct and indirect impacts - Qiong Zhang; Rui Liu; Jing Zhang; Yuxin Xie; Yuekai Ding; Weihua Yuan (Journal of Hydrology, 2026)

Reducing grain arsenic and extracting soil arsenic in paddies by an integrated ridge–furrow and ferrihydrite–PVA membrane system - Jing-Min Yang; Qiao-Rui Ren; Zi-Xin Liu; Xin Wang; Dong-Xing Guan; Ya-Nan Dai; He Pei; Bo Peng; Qin-Bo Qin (Journal of Environmental Sciences, 2026)

Recent progress on Cu-based MOF electrocatalysts for CO2 reduction - Heng-fei Cui; Xiao-jing Liu; Cong Liu; Hao-wen Zhu; Ming-yang Liu; Rui-tang Guo (Fuel, 2026)

Synergistic surface plasmon resonance effect of Ag and S-scheme heterojunction in Ag/AgBr/Bi24O31Cl10 towards enhanced enrofloxacin removal: Performance, degradation pathways and synergistic mechanism - Xiao-Ju Wen; Qian Zhan; Hongyu Ye; Jing Xu; Binbin Qian; Rui Luo; Xiankun Wu; Zongtang Liu; Zhenghao Fei; Hai Guo (Environmental Research, 2026)

Interfacial charge transfer bridge enables high-quality heterojunction for braided coaxial ammonium-ion asymmetric supercapacitors - Jing Xu; Sheng-Jie Wang; Mao-Lan Liao; Zi-Tao Yang; Jia-Peng Hu; Rui-Lai Liu; Jia-Huan Tang; Zhi-Feng Zheng; Yi-Bing Xie (Chemical Engineering Journal, 2026)

Integrated Aerobic Exercise and Multisensory Environment Training for Age-related Cognitive Decline via Hippocampal-prefrontal Neural Circuit Modulation - Huawei Lin; Yuxi Qiu; Zhongyi Hu; Liming Chen; Yaling Dai; Tao Jiang; Rui Li; Sinuo Wang; Yajun Cao; Jianhong Li; Huanhuan Liu; Yuwei Ye; et al. (Molecular Neurobiology, 2026)

A sustainable biochar system to significantly reduce global greenhouse gas emissions - Meng Tan; Jianwei Zhou; Peng Liu; Ziyi Zhou; Jinping Tang; Yingxiang Fei; Jing Shang; Xingjie Wang; Rui Qi (Mitigation and Adaptation Strategies for Global Change, 2026)

A facile and sensitive protein immune polyacrylamide gel electrophoresis with online fluorescent imaging - Rui Zou; Zixian Yu; Jing Gao; Qiang Zhang; Yiren Cao; Xiaoyi Lin; Yibing Peng; Weiwen Liu; Jianguang Wu; Chengxi Cao (Analytica Chimica Acta, 2026)

Robust building wireframe reconstruction: a hypergraph and transformer-enhanced framework for large-scale and real-world urban point clouds - Haoran Gong; Jing Liu; Rui Tong; Fuqiang Tian; Di Wang (International Journal of Remote Sensing, 2025)

7,8-Dihydroxyflavone ameliorates bone loss by regulating TRKB/AKT/FOXO3a pathway in a mouse model of alzheimer’s disease - Dong Liu; Xiaoxiong Li; Peng Shi; Wenjuan Hong; Jie Huang; Mingliang Hou; Linqiu Ma; Qirong Liao; Hongyan Yang; Xiaoyan Fu; Huadong Zhou; Jing Lu; et al. (Psychopharmacology, 2025)

Urinary metal mixtures and cataract: Findings from a U.S. population-based study and network pharmacology analysis - Runzi Yang; Jing Li; Rui Liu; Tingting Ren; Nan Wang; Liangyuan Xu; Jianmin Ma (Toxicology Letters, 2025)

Whole-genome resequencing unveils the phylogeographic coevolution of Oncomelania hupensis with Yangtze River dynamics in China - Lei Duan; Fang Luo; Qin Liu; Shen Chen; Xia Tian; Wen-Wen Lv; Lu He; Zi-Rui Ren; Jing Xu; Xiao-Nong Zhou; Shi-Zhu Li; Shan Lv; et al. (Molecular Phylogenetics and Evolution, 2025)

Efficient piezo-photocatalytic degradation of aqueous tetracycline over porous carbon nitride with detoxification analysis - Ning Liu; Yue Zhang; Pengxiao Liu; Zhihao Cheng; Li Kang; Rui Ma; Jing Lu (Journal of Environmental Chemical Engineering, 2025)

Engineering biopolymer-based nanocomplexes via self-assembly: sodium alginate-lignin hybrid nanoparticles for pH-triggered and sustain release of isorhamnetin - Yongkang Pan; Nannan Jing; Rui Li; Juanjuan Yi; Xin Liu; Jiaqing Zhu; Jike Lu (Food Research International, 2025)

Molecular sensory basis of the smoky aroma in sesame oil elucidated by combining SAFE-GC-O-MS, σ-τ plot, and computational simulations - Tian-Pei Zhao; Tong-Yu Wang; Yi Jiang; Yi-Fei Wang; Shu-Rui Zhang; Jing-Yu Chen; Yue-Hua Li; Xue-De Wang; Hua-Min Liu; Hong-Wei Liu; Ke-Qing Liu (Food Research International, 2025)

Nanoconfined Co3O4 in hollow carbon spheres unlocks synergistic nonradical pathways for superior persulfate activation - Rui Lv; Liying Wang; Jing Lan; Zongshan Zhao; Xiujun Liu; Congyun Zhang; Guoliang Li (Chemical Engineering Journal, 2025)

Upcycling PET waste into carbon quantum dots as flame retardant of PET for closed-loop recycling - Jianfei Wei; Guocong Ma; Yaoyao Tang; Jing Zhang; Gaoling Jin; Chaohui Ma; Linhan Bing; Zhiguo Zhu; Zhenfeng Dong; Puzhen He; Ruichen Zhou; Rui Wang; et al. (Chemical Engineering Journal, 2025)

High-yield synthesis of biomass-derived carbon dots for enhanced taraxacum growth - Guanxiong Liu; Hui Wang; Jiaxin Dong; Yinying He; Rui Wang; Xiangli Li; Dongyue Liu; Jing Duan; Jing Feng; Xiaoyu Lu; Lijuan Gui; Sheng Hou; et al. (Biomass and Bioenergy, 2025)

SARS-CoV-2 nucleocapsid protein induces a Mincle-dependent macrophage inflammatory response in acute kidney injury - Rui-zhi Tan; Wen-jing Zhao; Jing Gao; Hui-yao Lan; Jian Liu; Li Wang (Inflammation Research, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Melichumarin A, a new coumarin with nitric oxide inhibitory activity from the stems of Melicope chunii - Rui-Hong Zhu; Zi-Feng Liang; Zhong-Liu Zhou; Zi-Ming Chen; Qi Zhou; Jing-Ling Ren; Shou-Yuan Wu (Natural Product Research, 2025)

Research on Acoustic-Electrical Integrated Technology in Geothermal Resource Exploration, Development and Monitoring - Feng Chu; Rui Xu; Rong-hua Zhang; Yi-guo Xue; Deng-rui Wu; Lin-zhi Lang; Shu-ge Liu; Jing-kai Qu (Applied Geophysics, 2025)

Bioactive sulfur-containing amides from the leaves of Glycosmis lucida - Shou-Yuan Wu; Hong-Yan Yang; Zhong-Liu Zhou; Zi-Feng Liang; Rui-Hong Zhu; Jing-Ling Ren; Pei-Lian Liu; Zi-Ming Chen (Natural Product Research, 2025)

Populus euphratica PeMAX2 counteracts PeGRP2 to stabilize target mRNAs relating to salt tolerance - Jing Li; Jun Yao; Siyuan Ma; Jian Liu; Ziyan Zhao; Zhe Liu; Kexin Yin; Caixia Yan; Kaiyue Dong; Rui Shi; Nan Zhao; Rui Zhao; et al. (Plant Science, 2025)

The correlation between temperature change and lung cancer risk altered by air particulate pollutants: Nationwide analysis - Shenxuan Zhou; Yanchi Wang; Zhenyu Li; Yiran Liu; Rui Zhu; Bo Liu; Jiacan Yuan; Mingna Wu; Jing Xiao; Hanpeng Lai; Anhui Ning; Yan Zhang; et al. (Journal of Cleaner Production, 2025)

Millimeter-scale interactions of nitrogen and potassium on denitrification, anammox, and Feammox in soil fertilization zones - Jingjing Lyu; Rui Tian; Runhua Zhang; Peng Chen; Xinxin Jing; Runqin Zhang; Kang Zhao; Yi Liu; Chenhao Lyu; Zhiguo Li (Journal of Environmental Sciences, 2025)

Morphology and nutrient content of bamboo rhizomes: Responses to enclosure succession in a Phyllostachys edulis forest in Wuyi Mountains, China - Xing Cai; Rui Cheng; Zhenhua Chen; Jiannan Lin; Min Wu; Jiaying Liu; Jihong Xiao; Yuchen Lin; Lingyan Chen; Yirong Zhang; Jundong Rong; Tianyou He; et al. (Forest Ecology and Management, 2025)

Protective Effects of Deinoxanthin on Brain Oxidative Damage and Gut Microbiota in the D-Galactose-Induced Aging Mice - Huijuan Su; Yutao Li; Jiayi Wan; Jieyu Lin; Jiayao Wang; Rui Fan; Dingming Liu; Jing Wei; Hongbo Xin; Yuejin Hua; Shengjie Li (Molecular Neurobiology, 2025)

Prolonged sepsis triggers abnormal mitochondrial dynamics in the limb muscles and diaphragm - Chao Xiong; Fasheng Guan; Jianguo Feng; Jing Jia; Jumei Zhang; Rui Tu; Jie Li; Jun Zhou; Jianglin Wang; Li Liu (Molecular and Cellular Biochemistry, 2025)

Cassiterite U–Pb ages from the Tin Islands, Indonesia, the southern end of the Southeast Asian tin province - Jie-Hua Yang; Rui-Zhong Hu; Mei-Fu Zhou; Bernd Lehmann; Jun-Hong Zhao; Jing-Hua Wu; Liang Liu; Wei Mao; Zheng-Teng Cui; Mega Fatimah Rosana (Mineralium Deposita, 2025)

The Impact of the Combined Application of Zinc and Selenium on the Physiological Mechanisms and Mercury Accumulation in Rice Under Mercury Stress - Qiu Huang; Jing Liu; Wanyu Li; Anqi Xu; Rui Wu; Fanxin Qin (Bulletin of Environmental Contamination and Toxicology, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Synergistic engineering of four-pointed star-like layered stacking and oxygen vacancies toward high-efficiency Bi2O2-xSe photocatalysts for the degradation of tetracycline and Congo red - Yao Yang Liu; Zhong Li; Yi Liang; Jing Hao Zhuang; Wen Ji Zhang; Tao Tang; Yin Fen Cheng; Rui Ou; Bao Yue Zhang; Jian Zhen Ou (Journal of Environmental Chemical Engineering, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Dithiothreitol oxidative potential (OP) of PM2.5 in Beijing: Quantitative contribution of metals to OP and its prediction based on machine learning models - Yusheng Ma; Mengshuang Sheng; Jing Shang; Rui Tang; Jiong Cao; Yuhan Liu; Chenyu Liang; Yu Kuang; Yan Zheng; Zhen Cheng; Rico K.Y. Cheung; Robin L. Modini; et al. (Journal of Hazardous Materials, 2025)

Electrospun polylactic acid membranes containing Tartary buckwheat flavone extract for the preservation of green grapes - Jing Li; Liangping Zhang; Yuran Wang; Dayu Liu; Yongping Wen; Jian Wang; Rui Qi; Baohua Liu; Yin Zhang; Songzhi Xie (Food Chemistry, 2025)

Physicochemical characteristics, flavor profile, and microbial community of commercial traditional fermented chili pepper in Guizhou (Zao pepper) - Xijuan Zhang; Pei Gao; Qixing Jiang; Yongjun Wu; Shuhan Yang; Xiaojing Zhang; Rui Cao; Jing Wang; Min Jiang; Shaoquan Liu; Peipei Yu; Fang Yang; et al. (Food Bioscience, 2025)

A unique demersal fish fauna in the Chukchi Borderland, Central Arctic Ocean - Ran Zhang; Hai Li; Puqing Song; Rui Wang; Jing Zhang; Tianci Wang; Shusen Fu; Shigang Liu; Yuan Li; Xing Miao; Lei Yang; Longshan Lin (Reviews in Fish Biology and Fisheries, 2025)

Neuroprotective effects of Yangming-Kaixin-Yizhi formula in Alzheimer’s disease: dual regulation of PI3K/Akt and p38 MAPK signaling via network pharmacology and experimental approaches - Jing Lei; Jiaming Li; Wei Wu; Rui Xiong; Yao Liu; Yong Tang (Metabolic Brain Disease, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

Parapedobacter flavus sp. nov., isolated from padding of fermentation bed - Rui Wang; Yan-Yan Zheng; Zi-Xuan Liu; Xuan Zhang; You-Jun Liao; Ya-Jing Yu; Ai-Hua Li (Antonie van Leeuwenhoek, 2025)

Evolution and functional characterization of a biosynthetic gene cluster for saponin biosynthesis in Sapindaceae - Yingxiao Mai; Huimin Hu; Wenjuan Ji; Yaxuan Xiao; Hong Zhou; Zaohai Zeng; Wenshu Lv; Xingling Su; Jiakun Zheng; Jing Xu; Yanwei Hao; Zhenhua Liu; et al. (Molecular Plant, 2025)

Controllable synthesis of bimetallic Cu-Zn conjugated polymer microflowers with splendid laccase- and antioxidase-like activities for colorimetric detection of organic pollutants and eliminating cigarette smoke radicals - Shu-Chang Zhao; Dan Wu; Ya-Nan Kong; Jing-Jing Luo; Bo-Yi Yuan; Rui-Lin Liu (Journal of Hazardous Materials, 2025)

Effortless rule: Effects of oversized microplastic management on lettuce growth and the dynamics of antibiotic resistance genes from fertilization to harvest - Jing-Yuan Chen; Lin-Jie Qin; Tiao Long; Rui-Ting Wu; Shi-Hua Niu; Shuo Liu; Wei-Kang Deng; Xin-Di Liao; Si-Cheng Xing (Journal of Hazardous Materials, 2025)

Bipartite trophic levels cannot resist the interference of microplastics: A case study of submerged macrophytes and snail - Jun Chen; Zhiqiang Zhang; Nan Shen; Hongwei Yu; Guo Yu; Jing Qi; Rui Liu; Chengzhi Hu; Jiuhui Qu (Journal of Hazardous Materials, 2025)

Association between serum elementomics of 48 elements and female fecundity: evidence from a nested case-control study in China - Tian Tian; Fang Liu; Li Li; Jing Wei; Kailibinuer Kayimu; Yu Fu; Huahua Jiang; Fei Kong; Rui Yang; Yuanyuan Wang; Xiaoyu Long; Jie Qiao (International Journal of Hygiene and Environmental Health, 2025)

Isorhamnetin-lignin nanoparticles: green preparation, characterization, remarkable bioavailability and long-lasting bioactivity in vivo - Yongkang Pan; Rui Li; Nannan Jing; Juanjuan Yi; Xin Liu; Jike Lu; Jiaqing Zhu (Food Bioscience, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Soil myxomycete community in temperate cropland and influence of straw turnover - Feng-Yun Zhao; Guan-Xiu Guan; Rui-Xuan Xiang; Bai-You Chen; Jing Feng; Jian Liu (Applied Soil Ecology, 2025)

Macoligophones A–I, prenylated acetophenone dimers and monomers from Maclurodendron oligophlebium - Jing-Jing Qi; Yu-Nan Qian; Ying Li; Xiang-Yu Liu; Rui-Yao Fu; Zheng-Hui Huang; Jian-Min Yue; Jin-Xin Zhao (Phytochemistry, 2025)

Ectomycorrhizal fungi and biochar promote soil recalcitrant carbon increases under arsenic stress - Xuan Zhang; Yang Liu; Xingran Mo; Zhongliang Huang; Yonghua Zhu; Hui Li; Lijuan Jiang; Zhuming Tan; Zihao Yang; Yi Zhu; Jing Huang; Baiquan Zeng; et al. (Journal of Hazardous Materials, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Development of novel caffeic acid derivatives as multifunctional agents for the treatment of AD - Kerong Hu; Jing Yang; Qiyao Zhang; Xinxin Wang; Yujie Xu; Yuxin Zhang; Zhenghuai Tan; Wenmin Liu; Rui Chen; Zhipei Sang (Medicinal Chemistry Research, 2025)

CYP321F3 mediates metabolic resistance to methoxyfenozide in rice stem borer, Chilo suppressalis - Fang-Rui Guo; Shu-Chao Wang; Yan Liu; Shuai Wang; Jing-Mei Huang; Hao Sun; Lin-Feng He; Yuan Xie; Song-Tao Qiao; Feng-Xia Yang; Chris Bass; Cong-Fen Gao; et al. (Pesticide Biochemistry and Physiology, 2025)

Vanadium recovery with barium slag as a roasting additive: A novel waste-to-value approach - Hong-Rui Yue; Ya-Kun Zhao; Xiang-Xin Xue; Jing Liu (Journal of Cleaner Production, 2025)

Removal of arsenic from water by silver nanoparticles and Fe-Ce mixed oxide supported on polymeric anion exchanger - Li Li; Su-juan Yu; Rong-gang Zheng; Qing-cun Li; Rui Liu; Jing-fu Liu (Journal of Environmental Sciences, 2025)

Radiochromic perovskite La2MgZrO6:Pr for X-ray imaging and ionizing radiation detection - Zi-Hao Chen; Qiang Tang; Jian-An Zeng; Haijiao Xie; Rui Zou; Jing Wang; Bo-Mei Liu (Chemical Engineering Journal, 2025)

Research advances in branched-chain amino acid metabolism in tumors - Zheng Li; Sainan Chen; Xuechao Wu; Fei Liu; Jing Zhu; Jiayi Chen; Xiaojie Lu; Rui Chi (Molecular and Cellular Biochemistry, 2025)

Petrogenesis of Early Permian within-plate-type gabbros in the Western Qiangtang Terrane, Tibet: partial melting of lithospheric mantle metasomatized by subducted oceanic sediments on the northern margin of the Gondwana - Xiao-Rui Fan; Yun-Chuan Zeng; Ji-Feng Xu; Feng Huang; Ming-Jian Li; Xi-Jun Liu; Hong-Xia Yu; Jing Hu (International Geology Review, 2025)

Mechanism insight into sulfidated nano zero-valent iron/biochar activated persulfate for highly efficient degradation of p-chloroaniline - Jingchun Yan; Zihan Guo; Yuyuan Sun; Zichen Yan; Rui Liu; Yudong Chen; Jing Song (Chemosphere, 2025)

Advancements in artificial pollination of crops: from manual to autonomous - Leilei He; Xiaojuan Liu; Yusong Ding; Xudong Jing; Haojie Dang; Bryan Gilbert Murengami; Lamin L. Janneh; Rui Li; Spyros Fountas; Jayme Garcia Arnal Barbedo; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Static and fatigue characteristics of steel-lining reinforced pultruded BFRP square tube bolted joints: A comparative analysis on different adhesives - Jianxun Liu; Jing Wang; Xinlei Ma; Mengdie Liang; Rui Pei; Xin Wang; Zhishen Wu (Engineering Structures, 2025)

Atomically dispersed dual-active-site catalyst for enhanced oxygen reduction reaction: Synergistic effect of Fe and V in M−N−C structures - Qi-Dong Ruan; Rui Feng; Lu Liu; Lu Zhang; Jiu-Ju Feng; Yacheng Shi; Yi-Jing Gao; Ai-Jun Wang (Chemical Engineering Journal, 2025)

Clay Li isotopes reveal contrasting responses of chemical weathering intensity to hydroclimate changes in South Asia - Jingrui Li; Xuefa Shi; Shengfa Liu; Hui Zhang; Zhaowei Jing; Xiaoming Miao; Kaikai Wu; Rui Jiang; Somkiat Khokiattiwong; Narumol Kornkanitnan (Chemical Geology, 2025)

Research progress of non-coding RNA regulating the role of PANoptosis in diabetes mellitus and its complications - Guangyu Han; Kaibo Hu; Tianfeng Luo; Wenting Wang; Deju Zhang; Liu Ouyang; Xiao Liu; Jianping Liu; Yuting Wu; Jianqi Liang; Jitao Ling; Yixuan Chen; et al. (Apoptosis, 2025)

Combined uranium-series and trace elements analysis in cold seep bivalves: possibility in hundred-year-scale reconstruction of deep-sea temperature and acidification - Chaofeng Cai; Jing-Chun Feng; Guozhong Wu; Rui Hou; Xiao Chen; Jinyi Liu; Xiaochun Zhang; Si Zhang (Frontiers in Marine Science, 2025)
Despite the pivotal role of deep-sea in the global climate system, effective technology is still limited for reconstructing the key parameters of deep-sea environment such as temperature and acidification, especially at the hundred-year scale. In this study, we assessed the robustness and reliability of using bivalve shells in reconstructing cold seep environments. A significant heterogeneous distribution of trace elements was observed in the shells of clams and mussels from Formosa and Haima cold seeps even if they were collected from the same site, which was caused mainly by the environmental variables rather than physiological characters. The results of the principal component analysis revealed different trace elements ratios in the shell were associated with seepage. In particular, Sr/Ca was identified as a reliable proxy for temperature reconstruction, which performed better than oxygen isotopes. Na/Ca and U/Ca are potential proxies for cold seep acidification, but further validation is needed before their practical application. The age bias using the U-series dating method resulted from high 232 Th and low initial 230 Th/ 232 Th rather than from alpha-recoil processes. The median ages assigned to mussels from the F and Haima cold seeps were 229.5 and 323.5 years, respectively. The lifespan of clams from the Haima cold seep was too short to date accurately. We proposed to conduct feasibility verification and error correction to enhance the method performance in reconstructing the hundred-year evolution of cold seep environment in the South China Sea.

Effect of rhizosphere soil microenvironment interaction on ginsenoside content in Panax ginseng: A case study of three-year-old agricultural ginseng - Zhefeng Xu; Yuqiu Chen; Rui Liu; Yibing Wang; Chunshuo Liu; Jing Fang; Qinghe Zhang; Tao Zhang; Changbao Chen (Rhizosphere, 2025)

Ultrasound-assisted extraction of flavonoids from Rudbeckia hirta L. flowers using deep eutectic solvents: Optimization, HPLC analysis and anti-inflammatory activity - Jiang-Rui Wang; Yin-Long Li; Hai-Tao Zhang; Zhao-Bao Xiang; Jing Zuo; Bo Peng; Xing-Yu Liu; Hong Ou (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Structural characteristics and antioxidant activity of binary compounds formed by covalent modification of plant derived recombinant lactoferrin (OsrhLF) with four typical carbohydrates - Xiaoyan Guan; Kexin Wang; Yeting Wu; Jing Xu; Rui Liu; Zixian Xia; Yanchun Shao; Youyou Lu (Food Chemistry, 2025)

Three-Dimensional In Situ Stress Distribution in a Fault Fracture Reservoir, Linnan Sag, Bohai Bay Basin - Jiageng Liu; Yanzhong Wang; Jing Li; Xiaoyu Meng; Jiayi Teng; Zhicheng Wang; Mingzhi Li; Rui Zhu (Journal of Marine Science and Engineering, 2025)
The fault fracture body, consisting of faults, fracture zones, cracks, and the matrix, plays a crucial role in controlling oil and gas accumulation. Understanding its spatial distribution and analyzing the in situ stress field are essential for optimizing well design and fracturing operations. This study integrates geological, logging, and seismic data, and employs advanced techniques such as ant tracking to establish a skeletal model of the fault fracture body. Reverse modeling and optimization reconstruction are used to construct a three-dimensional geomechanical model of the fracture system. Machine learning techniques, specifically a back propagation (BP) neural network, are utilized to invert the boundary conditions of the study area. Finite element numerical simulation software is then applied to model the three-dimensional in situ stress field under coupled flow–solid interaction. The reservoirs in the study area are characterized by a dense structure, low porosity, and low permeability. The results indicate that the maximum horizontal principal stress in the fault fracture reservoir ranges from 68.0 to 72.8 MPa, while the minimum horizontal principal stress ranges from 58.2 to 63.1 MPa. The stress at fractures is lower than that in the surrounding matrix, and stress concentrations occur at both ends of the faults. The in situ stress field exhibits distinct subarea characteristics, with significant stress reductions across fault fractures and directional deflections at faults. These findings provide valuable insights for improving reservoir development efficiency and optimizing well operations in similar geological settings.

Monitor and classify dough based on color image with deep learning - Bryan Gilbert Murengami; Xudong Jing; Hanhui Jiang; Xiaojuan Liu; Wulan Mao; Yuedan Li; Xueyong Chen; Shaojin Wang; Rui Li; Longsheng Fu (Journal of Food Engineering, 2025)

Arsenic methylation and microbial communities in paddy soils under alternating anoxic and oxic conditions - Jing Liu; Rui Pei; Runzeng Liu; Chuanyong Jing; Wenjing Liu (Journal of Environmental Sciences, 2025)

Analytical solutions of two-liner tunnels constructed in time-dependent plastic rocks considering loading-unloading stress paths - Hua-ning Wang; Qian Liu; Fei Song; Rui-cong Fu; Ming-jing Jiang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Mechanistic insight into the neurodevelopmental toxicity of the novel pesticide pyrifluquinazon (PFQ) and its major metabolite in early-life stage zebrafish - Rui Huang; Zijun Liu; Yunrui Pan; Zheng Ma; Huili Wang; Bin Wan; Jianzhong Li; Jing Chang (Environmental Pollution, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Spatial Characteristics of the Plasma Spark Source Wavelet - Jia Wei; Xiaozhu Hao; Jing Feng; Rui Yang; Lei Xing; Huaishan Liu; Wei Wang; Zhiqiang Wu; Dong Zhang; Linwei Li (Journal of Ocean University of China, 2025)

Foxa1 disruption enhances human cell integration in human-mouse interspecies chimeras - Li-na Wang; Jun-shuang Jia; Xing-long Yang; Yue-ting Wen; Jing-xian Liu; Deng-ke Li; Xing-rui Chen; Jia-hong Wang; Ji-ke Li; Zhong-xi Huang; Kai-tai Yao (Cell and Tissue Research, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Assessment of myelination development in neonatal rats using chemical exchange saturation transfer (CEST) 7-T MRI - Rui Wang; Shuxian Xu; Fenglin Jia; Yi Liao; Jiayi Li; Jing Liu; Fengyan Zhao; Haibo Qu (Experimental Brain Research, 2025)

Nanozymes featuring a mesoporous silica shell for rapid enrichment and ultrasensitive lateral flow immunoassay of influenza A - Jing Liang; Xiaoxian Liu; Zhenzhen Liu; Xuanming Xu; Yinuo Sun; Yuan Chen; Rui Xiao; Yajie Wang (Analytica Chimica Acta, 2025)

Flowering delay in apple could alleviate frost-induced yield loss under climate change in China - Renwei Chen; Jing Wang; Bin Wang; Yang Li; Rui Bai; Mingxia Huang; Zhenjiang Qu; Lu Liu (Agricultural and Forest Meteorology, 2025)

β-Caryophyllene oxide inhibits lysine acetylation of histones in Fusarium proliferatum to block ribosomal biosynthesis and function - Hong-Xin Liao; Jing Yang; Jin-Rui Wen; Hong-Yan Nie; Jun Zhao; Fu-Rong Xu; Xiao-Yun Liu; Xian Dong (Pesticide Biochemistry and Physiology, 2024)

Holocene paleoenvironment of the Nihewan Basin, China, inferred from high-resolution luminescence dating and a multiproxy analysis of gully sediments - Qing-Hao Ma; Yu-Jie Guo; Hua-Rui Lei; Yu-He Shen; Jia-Jing Wang; Ya Liu; Zhen-Yu Zhou; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Spatial patterns, source apportionment, and risk assessment of polychlorinated biphenyls (PCBs) in the surface sediments of eastern China lakes along a latitudinal gradient: Insights guided by full-congener analysis - Jing Dong; Xingru Zhao; Ran Dai; Rui Guo; Chengyou Liu; Xiaoai Cui; Yaqing Liu; Hui Wang; Binghui Zheng (Journal of Hazardous Materials, 2024)

Comparative study of pre- and post-Cu modified calcium-based desulfurizers: Experimental and theoretical insights into adsorption vs. catalysis - Xiaodong Liao; Yulu Liu; Zongshe Liu; Qisong Liu; Wanglai Cen; Rui Fan; Long Li; Jing Shao; Yuxiao Shi (Journal of Environmental Chemical Engineering, 2024)

SoftFormer: SAR-optical fusion transformer for urban land use and land cover classification - Rui Liu; Jing Ling; Hongsheng Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Impact of the long-term storage on flavor quality of Liupao tea using sensory evaluation combined with metabolomics analysis - Yingyi Huang; Huahong Liu; Jing Wang; Rui Zhang; Yun Zhang; Zhusheng Liu; Yuelan Pang; Chun Yang; Jinfang Nie (Food Research International, 2024)

Grazing reduced vegetation biomass and root nutrition related to plateau zokor creating mounds in summer on the Tibetan Plateau - Zhiying Zhang; Bin Chu; Limin Hua; Rui Dong; Kechi Dong; Xincheng Cai; Jize Liu; Ruixun Gan; Longming Dong; Jing Zhang; Wenqian Sun; Jian Sun; et al. (Ecological Engineering, 2024)

Improved nitrate removal by polyvinyl alcohol/sodium alginate hydrogel beads entrapping salt-tolerant composite bioagent AHM M3 - Rui Han; Hongjing Ma; Xin Su; Jing Song; Peiwu Liu; Yinghai Wu; Ying Liu (Desalination, 2024)

Molecular engineering in thizolo[5,4-d]thiazole-based donor-acceptor covalent organic framework Induced high-efficient photosynthesis of H2O2 - Ding-Ming Xue; Yi-Jun Zhang; Jing-Wen Chen; Hao Yang; Rui-Jie Xie; Shi-Chao Qi; Yuan-Qing Bu; Fei Liu; Hou-Hu Zhang; Jacques Lalevée (Chemical Engineering Journal, 2024)

Study of the effect of keap1 on oxidative stress in human umbilical cord mesenchymal stem cells - Hongrong Deng; Yunxia Chen; Huiwen Liu; Li Wang; Hao Xu; Bin Tan; Qin Yi; Rui Wang; Bolin He; Jie Tian; Jing Zhu (Molecular Biology Reports, 2024)
Background HucMSCs had shown promising efficacy in treating childhood diseases, but oxidative stress induced by the poor microenvironment at the site of damage resulted in low cell survival after transplantation, thus preventing the cells from maximizing therapeutic efficacy. Therefore, this study aimed to investigate the role and mechanism of keap1 in oxidative stress injury of human umbilical cord mesenchymal stem cells (hucMSCs), and to provide theoretical support for improving the efficacy of stem cell therapy. Methods The hucMSCs were treated with hypoxic low-sugar-free serum (GSDH) to mimic the damaged site microenvironment after implantation. Adenoviral overexpression of keap1 gene of hucMSCs was performed in vitro, and cell proliferation ability was detected by CCK8 assay, crystal violet staining assay, and cell cycle assay. Cellular redox level was assessed by Amplex Red, MDA, and GSH/GSSG kit. Mitochondrial morphology was evaluated by mitotracker Red staining. ATP production was estimated by ATP detection kit. The mRNA and protein expression levels were tested by western blotting and RT-qPCR. Results GSDH treatment substantially upregulated keap1 expression. Subsequently, we found that overexpression of keap1 notably inhibited cell proliferation and caused cells to stagnate in G1 phase. At the same time, overexpression of keap1 induced the production of large amounts of H 2 O 2 and the accumulation of MDA, but suppressed the GSH/GSSG ratio and the expression of antioxidant proteins NQO1 and SOD1, which caused oxidative stress damage. Overexpression of keap1 induced cells to produce a large number of dysfunctional mitochondria resulting in reduced ATP production. Moreover, Overexpression of keap1 significantly decreased the IKKβ protein level, while upregulating IkB mRNA levels and downregulating P50 mRNA levels. Conclusions Overexpression of keap1 may induce oxidative stress injury in hucMSCs by down-regulating IKKβ expression and inhibiting NF-κB pathway activation. This implies the importance of keap1 in hucMSCs and it may be a potential gene for genetic modification of hucMSCs.

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Quantifying spatial interaction centrality in urban population mobility: A mobility feature- and network topology-based locational measure - Jing Cai; Rui Li; Zhaohui Liu; Xinrui Liu; Huayi Wu (Sustainable Cities and Society, 2024)

Comparison of prenatal and postnatal exposure to neonicotinoids and their temporal trends in breast milk - Kaiqin Huang; Meiqing Lin; Jing Yi; Guocheng Liu; Rui Hua; Yangyang Liu; Yanji Qu; Cairong Chen; Shengtao Ma (Science of The Total Environment, 2024)

Unveiling the synergism and reaction pathway of ethyl acetate removal in DBD/absorption integrated reactor - Li-qiang Qi; Lin Huang; Jia-yue Lei; Rui Dai; Fan Du; Bo Wang; Jing-xin Li; Feng Liu (Process Safety and Environmental Protection, 2024)

Myosuppressin signaling deficiency affects ovarian development via repression of 20-hydroxyecdysone biosynthesis in Grapholita molesta - Jie Cheng; Jing-Kai Liu; Tian-Li Wang; Wei Wei; Hui-Ming Xiang; Xian-Wei Li; Rui-Yan Ma; Zhi-Guo Zhao (Pesticide Biochemistry and Physiology, 2024)

Half-antibody spur one-to-one recognition mechanism can function with chemical-staining technology for next-generation lateral flow immunoassay - Jingke Xu; Jing Zhou; Kai Liu; Tong Bu; Leina Dou; Rui Shu; Sijie Liu; Shaochi Wang; Xuechi Yin; Daohong Zhang; Ruiling Zhang; Jie Cheng; et al. (Chemical Engineering Journal, 2024)

“Four-in-One” multifunctional nanohybrids integrated magnetic colorimetric catalytic SERS-driven lateral flow immunoassay for ultrasensitive detection of MPXV - Xiaoxian Liu; Xingsheng Yang; Zongzheng Zhao; Xiao Li; Jing Liang; Yinuo Sun; Rui Xiao; Guanghui Wang (Chemical Engineering Journal, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

A comprehensive conceptual framework for signaling in-lake CO2 through dissolved organic matter - Maofei Ni; Rui Liu; Weijun Luo; Junbing Pu; Shengjun Wu; Zhikang Wang; Jing Zhang; Xiaodan Wang; Yongmei Ma (Water Research, 2024)

Reaction mechanism for NH3-SCR of NOx over CrMn1.5O4 catalyst - Zheng-nan Yuan; Rui-tang Guo; Xiao-jing Liu; Yi-feng Xu; Lu Liu; Wei-guo Pan (Fuel, 2024)

Relationship between microorganisms and the flavour of douchi obtained from different regions: Analysis using high-throughput sequencing and GC–MS - Rui Zhang; Jing Li; Xiaoqing Miao; Zhiyuan Song; Shan Jiang; Aidong Liu (Food Bioscience, 2024)

An effective potential Bifidobacterium animalis F1-7 delivery strategy: Supramolecular hydrogel - sodium alginate/tryptophan-Sulfobutylether-β-cyclodextrin (Alg/Trp-SBE-β-CD) - Xiaoyang Huang; Jing Wang; Rui Liu; Chunrong Yang; Yanchun Shao; Xiaohong Wang; Huaxi Yi; Youyou Lu (Food Hydrocolloids, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

High-altitude exposure leads to increased modularity of brain functional network with the increased occupation of attention resources in early processing of visual working memory - Jing Zhou; Nian-Nian Wang; Xiao-Yan Huang; Rui Su; Hao Li; Hai-Lin Ma; Ming Liu; De-Long Zhang (Cognitive Neurodynamics, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Short-term exposure to ambient fine particulate matter constituents and myocardial infarction mortality - Yingxin Li; Bing Lu; Jing Wei; Qingqing Wang; Wancheng Ma; Rui Wang; Ruijun Xu; Zihua Zhong; Lu Luo; Xi Chen; Ziquan Lv; Suli Huang; et al. (Chemosphere, 2024)

Higher risk of spring frost under future climate change across China's apple planting regions - Renwei Chen; Jing Wang; Yang Li; Rui Bai; Mingxia Huang; Zhenzhen Zhang; Lingxuan Zhao; Zhenjiang Qu; Lu Liu (European Journal of Agronomy, 2024)

Feasibility and safety of percutaneous intramyocardial septal cryoablation: A canine model with 6-month follow-up - Xiaonan Lu; Jing Li; David H. Hsi; Juan Zhang; Yupeng Han; Shengjun Ta; Jing Wang; Jin He; Jia Zhao; Chao Han; Lu Yao; Xumei Ou; et al. (Cryobiology, 2024)

Strategies, perspectives, and challenges of improving the initial coulombic efficiency and tap density of Sn-based anode materials for lithium-ion batteries - Hui Liu; Shuzhong Wang; Lu Liu; Junan Zhao; Wenjin Zhang; Rui Bao; Lijie Wang; Jianqiao Yang; Yanhui Li; Zefeng Jing (Chemical Engineering Journal, 2024)

Quantile delta-mapped spatial disaggregation analysis for summertime compound extremes over China - Rui Zhao; Xiong Zhou; Yongping Li; Jing Liu; Guohe Huang; Pangpang Gao (Climate Dynamics, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

The effects and mechanisms of heat stress on mammalian oocyte and embryo development - L.I. Lang; Zhen-zhen Wang; Bin Liu; S.H.E.N. Chang-qing; T.U. Jing-yi; W.A.N.G. Shi-cheng; L.E.I. Rui-ling; P.E.N.G. Si-qi; X.I.A.O. Xiong; Z.H.A.O. Yong-ju; Xiao-yan Qiu (Journal of Thermal Biology, 2024)

A novel, green, and environmentally friendly PBS/nano-CaCO3 hybrid membrane - Ming Jing; Yanhong Ji; Liuchun Zheng; Xi Liu; Zunbo Han; Jiayi Cai; Rui Bai; Benqiao He (Journal of Environmental Chemical Engineering, 2024)

The transport of bismuth in HCl-bearing aqueous vapour and low-density aqueous supercritical fluids: Implications for natural systems - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Qi Liu; Fei-Xiang Liu; Yuan Mei; Zi-Qi Jiang; Lin-Bo Shang; Jing-Jing Zhu; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2024)

Diagnostic performance of mpox virus (MPXV) real-time PCR assays: multicenter assessment and extended sensitivity analysis - Ziqiang Li; Yuqing Chen; Yanxi Han; Zhenli Diao; Tao Huang; Lei Feng; Yu Ma; Cong Liu; Meng Tian; Jing Li; Wanyu Feng; Zihong Zhao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Assessing the ecological security of the Three Gorges reservoir complex ecosystem based on the improved three-dimensional emergy ecological footprint model - Peiran Jing; Jinbao Sheng; Yi Wang; Tiesong Hu; Lidan Guo; Rui Zhu; Kai Dong; Ali Mahmoud; Yong Liu; Xiang Li (Science of The Total Environment, 2024)

Populus euphratica R2R3-MYB transcription factor RAX2 binds ANN1 promoter to increase cadmium enrichment in Arabidopsis - Caixia Yan; Bing Feng; Ziyan Zhao; Ying Zhang; Kexin Yin; Yi Liu; Xiaomeng Zhang; Jian Liu; Jing Li; Rui Zhao; Nan Zhao; Xiaoyang Zhou; et al. (Plant Science, 2024)

The cellular response and molecular mechanism of superoxide dismutase interacting with superparamagnetic iron oxide nanoparticles - Hao Ju; Yue Liu; Yameng Wang; Rui Lu; Bin Yang; Deyi Wang; Jing Wang (NanoImpact, 2024)

Hydrogen-donating behavior and hydrogen-shuttling mechanism of liquefaction solvents under Fe- and Ni-based catalysts - Haiyun Liu; Rui Zhang; Xin Zheng; Jing Xie; Bowen Tang; Zhi Li; Erguang Guo; Haoquan Hu; Lijun Jin (Fuel, 2024)

A NIR-II quantum dot-assisted dual-color imaging strategy enables simultaneous tracking of two subtypes of extracellular vesicles in vivo - Xing-Chi Liu; He-Jing Zhang; Rui Xu; Jing Liu; Hou-Fu Xia; Qi-Hui Xie; Zhi-Quan Tian; Zi-Li Yu; Gang Chen (Chemical Engineering Journal, 2024)

Cu-based bubble and ion sieve for ampere-level hydrogen evolution - Si-Wei Yan; Chuan-Qi Cheng; Fei-Fei Zhang; Ze-Yu Zhang; Kui Lin; Peng-Fei Yin; Rui Zhang; Jing Yang; Cun-Ku Dong; Jing Mao; Hui Liu; Xi-Wen Du (Chemical Engineering Journal, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Soil erosion is a major drive for nano & micro-plastics to enter riverine systems from cultivated land - Yanting Wang; Siyuan Jing; Peiyu Hou; Rui Ni; Lili Niu; Thomas Cherico Wanger; Weiping Liu; Kai Liu (Water Research, 2024)

In situ profiling reveals spatially metabolic injury in the initiation of polystyrene nanoplastic-derived intestinal epithelial injury in mice - Xianan Zhang; Jing Wang; Yuansheng Liu; Hemin Wang; Bin Li; Qing Li; Yi Wang; Yuru Zong; Jiajia Wang; Qingtao Meng; Shenshen Wu; Rongzhang Hao; et al. (Science of The Total Environment, 2024)

MOF derived highly dispersed bimetallic Fe-Ni nitrogen-doped carbon for enhanced peroxymonosulfate activation and tetracycline degradation - Lingyun Jing; Shasha Liu; Tong Wang; Zeqiang Zhang; Xia Zhao; Zhili Sun; Pengbo Hao; Yeqiang Hu; Wenhan Yang; Rui Quan; Xinyong Li; Dongnian Zhang; et al. (Journal of Environmental Chemical Engineering, 2024)

Synergistic multifactor influence and management of commercial vanadium-based catalyst lifetimes - Yi-feng Xu; Xiao-jing Liu; Rui-tang Guo; Tong Wu; Hong-lei Ding; Dong Ye; Wei-guo Pan (Fuel, 2024)

Correlation of glass transition features and macroscopic, mesoscopic properties of dough regulated by molecular weight of dextran - Shunqin Li; Jing Mao; Yunjiao Zhao; Wenjie Sui; Tao Wu; Rui Liu; Min Zhang (Food Hydrocolloids, 2024)

Study on the effect of NO2 impurity gas on the performance and local current density distribution of PEMFC - Rui Lin; Yuan Jing; Wenbo Dai; Shiyang Hua; Dengcheng Liu; Zhixian Hao (Chemical Engineering Journal, 2024)

Manipulating cationic ordering toward highly efficient and zero-thermal-quenching cyan photoluminescence - Hongzhi Zhang; Hong Li; Conglin Liu; Hongming Jiang; Junpeng Li; Yuxin Liu; Jiayi He; Rui Wang; Wanbiao Hu; Jing Zhu (Chemical Engineering Journal, 2024)

Variations in Column Concentration of Greenhouse Gases in China and Their Response to the 2015–2016 El Niño Event - Ningwei Liu; Lingjun Xia; Youjun Dou; Shaorou Dong; Jing Wen; Ying Wang; Rui Feng; Ruonan Wang; Yuhe Li (Journal of Meteorological Research, 2024)

Characteristics of typical intermediate and semi volatile organic compounds in Shanghai during China International Import Expo event - Taikui An; Yingjie Li; Rui Wang; Sheng'ao Jing; Yaqin Gao; Shuyu Liu; Dandan Huang; Min Zhou; Haixia Dai; Cheng Huang; Jun Lu; Hongli Wang; et al. (Chemosphere, 2024)

Redox condition changes caused by impacts: Insights from Chang’e-5 lunar glass beads - Runlian Pang; Jing Yang; Rui Li; Shirong Liu; Qiong Li; Dan Zhu; Wei Du; Yun Liu (Science Bulletin, 2024)

Biotemplated fabrication of N/O co-doped porous carbon confined spinel NiFe2O4 heterostructured mimetics for triple-mode sensing of antioxidants and ameliorating packaging properties - Yuan Gao; Juan Wang; Lin-Lan Zhao; Bo-Yi Yuan; Ya-Nan Kong; Jing-Jing Luo; Shu-Chang Zhao; Wei-Ming Yang; Rui-Lin Liu (Food Chemistry, 2024)

Mechanistic insights into the stepwise lithium-mediated electrochemical nitrogen reduction for enhanced ammonia synthesis - Peng Yang; Feng Gong; Chaozhen Liu; Shenglin Liu; Enkang Fu; Yuhang Jing; Junjie Feng; Wenbo Tang; Rui Xiao (Chemical Engineering Journal, 2024)

Vanadium isotope evidence for seawater contribution to V enrichment/mineralization in early Cambrian metalliferous black shales - Lin-Hui Dong; Wei Wei; Lingang Xu; Yi-Bo Lin; Ze-Rui Liu; Songqi Pan; Zhenhua Jing; Fang Huang (Science Bulletin, 2024)

Improving prediction of soil heavy metal(loid) concentration by developing a combined Co-kriging and geographically and temporally weighted regression (GTWR) model - Huijuan Wang; Menglu Zhao; Xinmiao Huang; Xiaoyong Song; Boya Cai; Rui Tang; Jiaxun Sun; Zilin Han; Jing Yang; Yafeng Liu; Zhengqiu Fan (Journal of Hazardous Materials, 2024)

Complete genome sequence of a novel dsRNA virus from the phytopathogenic fungus Fusarium oxysporum - Jing Wang; Yunxia Ni; Hui Zhao; Xintao Liu; Rui Qiu; Shujun Li; Hongyan Liu (Archives of Virology, 2024)

Investigating the spatio–temporal characteristics of lower atmospheric ducts across the China seas by performing a long–term simulation using the WRF model - Qi Liu; Xiaofeng Zhao; Jing Zou; Tong Hu; Zhijin Qiu; Bo Wang; Zhiqian Li; Chaoran Cui; Rui Cao (Frontiers in Marine Science, 2024)
In this work, a diagnostic scheme for lower atmospheric ducts was established based on the Weather Research and Forecasting (WRF) model. More specifically, a 10-year simulation test was conducted for the China seas to investigate the spatio-temporal characteristics of the lower atmospheric ducts phenomenon. Compared with the sounding data, the long-term simulations showed a high temporal correlation and the root mean square error of the modified atmospheric refractivity remained between 4 M and 7 M. Based on the simulations, significant regional differences in the occurrence probability of lower atmospheric ducts were detected from south to north. Among them, the surface ducts near the sea surface exhibited the highest occurrence probability, with higher probabilities being recorded in autumn and winter, and the probability gradually increased with the decreasing latitude. The spatio-temporal characteristics of duct height, thickness, and strength were generally consistent. In the seas at mid-latitudes, strong ducts mostly occurred in the spring and autumn, with the single-layer ducts being predominant and the first layer duct showing stronger characteristics than the second layer. In the lower latitude regions, the situation was exactly the opposite. The first duct layer, which existed throughout the year, exhibited weaker characteristics with less pronounced seasonal variations. On the other hand, the second duct layer demonstrated stronger features.

Endophytic Enterobacter sp. YG-14 mediated arsenic mobilization through siderophore and its role in enhancing phytostabilization - Jiawei Chen; Xuan Zhang; Min Kuang; Kunpeng Cui; Ting Xu; Xuanming Liu; Rui Zhuo; Ziwei Qin; Zhigang Bu; Zhongliang Huang; Hui Li; Jing Huang; et al. (Journal of Hazardous Materials, 2024)

A programmable quantum dot nanosensor guided by three-way junction skeleton-mediated cascade signal amplification for sensitive detection of circRNAs in breast cancer - Wen-jing Liu; Rui Song; Dongming Yang; Shulin Zhao; Chun-yang Zhang (Chemical Engineering Journal, 2024)

Chameleon-inspired supramolecular materials based on cucurbit[7]uril and viologens exhibiting full-color tunable photochromic behavior - Dong-Xue Xia; Xin Wang; Wen-Qi Sun; Rui-Lian Lin; Jing-Xin Liu; Ying-Wei Yang (Chemical Engineering Journal, 2024)

Fucosylated chondroitin sulfate from sea cucumber Stichopus chloronotus alleviate the intestinal barrier injury and oxidative stress damage in vitro and in vivo - Huanan Yin; Rui Li; Jing Liu; Yanying Sun; Lei Zhao; Jiaojiao Mou; Jie Yang (Carbohydrate Polymers, 2024)

The residues and health risk assessment of polychlorinated biphenyls (PCBs) in Pheretima (an earthworm-derived traditional medicine) from southeastern China - Yun-Jing Zhang; Jing Sun; Xiao-Jiang Chen; Rui Cheng; Zhi-Tong Liu; Ling Cao; You-Long Feng (Environmental Science and Pollution Research, 2024)

Individual ambient ozone exposure during pregnancy and adverse birth outcomes: Exploration of the potentially vulnerable windows - Chenqing Zhang; Jie Yang; Jing Wei; Yuansheng Liu; Huiping Zhu; Xiaobo Li; Jiajia Wang; Rui Chen (Journal of Hazardous Materials, 2024)

Analysis of soot formation and oxidation processes in the diesel engine fueled by n-octanol/biodiesel blends based on a detailed soot population balance model - Jing Li; Shiqi Gong; Yifei Liang; Shaohua Wu; Rui Liu; Wenming Yang (Fuel, 2024)

Numerical investigation on the spray characteristics of biodiesel with gas-assisted atomization injection - Rui Liu; Lingfeng Zhong; Songhong Li; Jing Li; Haocheng Ji (Fuel, 2024)

Physicochemical, microbiological and metabolomics changes in yogurt supplemented with lactosucrose - Rui Xue; Jing Liu; Min Zhang; Tariq Aziz; Shifa Felemban; Manal M Khowdiary; Zhennai Yang (Food Research International, 2024)

Involvement of TLRs/NF-κB/ESE-1 signaling pathway in T-2 toxin-induced cartilage matrix degradation - Yawen Shi; Rui Wang; Yanan Li; Yixin Cui; Ying He; Hui Wang; Yinan Liu; Meng Zhang; Yonghui Chen; Mingzhao Jia; Kunpan Chen; Xingran Ruan; et al. (Environmental Pollution, 2024)

High-performance Bi0.4Sb1.6Te3 alloy prepared by a low-cost method for wearable real-time power supply and local cooling - Xingzhong Zhang; Ziyu Wang; Yue Hou; Yong Liu; Liangwei Hu; Wenhao Xie; Jing Shi; Jianhong Wei; Rui Xiong (Chemical Engineering Journal, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

Short-term exposure to ambient air pollution and hospital admissions for angina among older adults in South China - Luxi Xu; Ruijun Xu; Yunshao Ye; Rui Wang; Jing Wei; Chunxiang Shi; Qiaoxuan Lin; Ziquan Lv; Suli Huang; Qi Tian; Yuewei Liu (Atmospheric Environment, 2024)

Hydrogen sulfide promoted cell differentiation, antioxidant ability, and flavonoids accumulation in Ginkgo biloba L. suspension cells - Jin-ling Lu; Yu-chen Hu; Ying Chen; Rui Liu; Jing-jing Di; Ting-ting Feng; Fu-liang Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Integrating bulk-RNA sequencing and single-cell sequencing analyses to characterize adenosine-enriched tumor microenvironment landscape and develop an adenosine-related prognostic signature predicting immunotherapy in lung adenocarcinoma - Tao Han; Jing Wu; Yafeng Liu; Jiawei Zhou; Rui Miao; Jianqiang Guo; Zhi Xu; Yingru Xing; Ying Bai; Dong Hu (Functional & Integrative Genomics, 2024)

Blood Pressure Estimation Based on PPG and ECG Signals Using Knowledge Distillation - Hui Tang; Gang Ma; Lishen Qiu; Lesong Zheng; Rui Bao; Jing Liu; Lirong Wang (Cardiovascular Engineering and Technology, 2024)

Speciation analysis and toxicity evaluation of arsenolipids—an overview focusing on sea food - Caiyan Li; Jing Chen; Zhuo Wang; Bingbing Song; Kit-Leong Cheung; Jianping Chen; Rui Li; Xiaofei Liu; Xuejing Jia; Sai-Yi Zhong (Archives of Toxicology, 2024)

Seasonal variations of microplastics in surface water and sediment in an inland river drinking water source in southern China - Wenyu Zhao; Jing Li; Mengyue Liu; Rui Wang; Boxuan Zhang; Xiang-Zhou Meng; Shengwei Zhang (Science of The Total Environment, 2024)

Degradation profile of environmental pollutant 17β-estradiol by human intestinal fungus Aspergillus niger RG13B1 and characterization of genes involved in its degradation - Qi-Meng Zhu; Chao Wang; Jing-Wen Liu; Rui Zhang; Xiu-Lan Xin; Juan Zhang; Cheng-Peng Sun; Xiao-Chi Ma (Journal of Hazardous Materials, 2024)

Effects of UHPC shear key on strengthening shear performances of wet joint in prefabricated composite beams - Hao Wang; Ning Wang; Xiao-gang Liu; Qing-rui Yue; Jing-liang Yan; Yu Zhang (Engineering Structures, 2024)

Membrane fouling mitigation and EPS reduction by CNTs-TiO2-PEDOT modified anode-membrane in Membrane Electro-Bioreactor (MEBR) treating mariculture wastewater - Jing Song; Yihan Li; Shihan Wang; Rui Han; Yu Ba; Ying Liu; Shengqiang Fan (Desalination, 2024)

The Protective Effect of Chronic Intermittent Hypobaric Hypoxia on Preventing the Destruction of CD34+ Haematopoietic Stem Cells in Aplastic Anaemia by Modulating the Th1/Th2 Balance - Hui Guo; Yilin Zhao; Rui Mu; Guangdao Zhang; Shuxian Chen; Xinwei Cao; Kangcan Liu; Yiran Liu; Baiyun Dai; Yuan Zhou; Chuan Wang; Jing Yang (Stem Cell Reviews and Reports, 2024)

Unexpected shifts of dissolved carbon biogeochemistry caused by anthropogenic disturbances in karst rivers - Maofei Ni; Rui Liu; Weijun Luo; Junbing Pu; Jing Zhang; Xiaodan Wang (Water Research, 2023)

TBtools-II: A “one for all, all for one” bioinformatics platform for biological big-data mining - Chengjie Chen; Ya Wu; Jiawei Li; Xiao Wang; Zaohai Zeng; Jing Xu; Yuanlong Liu; Junting Feng; Hao Chen; Yehua He; Rui Xia (Molecular Plant, 2023)

Mechanistic insight into the hydrogen transfer pathway for selective upcycling of PET to arenes - Huiyu Liu; Jun Zhang; Jing Gu; Rui Shan; Haoran Yuan; Yong Chen (Journal of Cleaner Production, 2023)

Assessment of cruise ship decarbonization potential with alternative fuels based on MILP model and cabin space limitation - Wenxian Zhang; Yuan He; Nianyuan Wu; Fuzheng Zhang; Danni Lu; Zekun Liu; Rui Jing; Yingru Zhao (Journal of Cleaner Production, 2023)

Linear relationship between CH4 fluxes and atmospheric CO2 concentration levels controlled by rice biomass and soil methanogenic communities - Yuanyuan Wang; Zhenghua Hu; Shuqi He; Qiang Jing; Lidong Shen; Chao Liu; Zhurong Wu; Wei Huang; Guihua Lu; Rui Cao; Kezhi Zheng; Ning Dong; et al. (Nutrient Cycling in Agroecosystems, 2023)

Reduced attention on restricted organochlorine pesticides, whereas still noteworthy of the impact on the deep soil and groundwater: a historical site study in southern China - Changlin Xu; Yue Cai; Rui Wang; Jing Wu; Guoyi Yang; Yahui Lv; Dehong Liu; Yu Deng; Yaqi Zhu; Qing Zhang; Lijun Wang; Shengwei Zhang (Environmental Geochemistry and Health, 2023)

Human amnion-derived mesenchymal stem cells improve subclinical hypothyroidism by immunocompetence mediating apoptosis inhibition on thyroid cells in aged mice - Chuyu Li; Qiang Rui; Xiaohan Dong; Song Ning; Jing Zhou; Huimin Wu; Chunyan Jiang; Yugui Cui; Jiayin Liu; Jun Jiang; Lianju Qin (Cell and Tissue Research, 2023)
Subclinical hypothyroidism (SCH) affects 10% of the global population, which is most prevalent in women and the elderly. However, it remains debatable whether the elderly with subclinical hypothyroidism needs thyroxine supplement. Human amnion-derived mesenchymal stem cells (hAMSCs) could play important roles in autoimmune diseases, suggesting that hAMSC be a candidate to regulate the thyroid function of female age-related subclinical hypothyroidism. Herein, we established the model of SCH in the aged female mice. This study was designed to investigate whether human amnion-derived mesenchymal stem cells (hAMSC) could effect on immune regulation, apoptosis inhibition of thyroid cells, thyroid function, blood lipid levels, and heart function. In addition, qualified hAMSCs were intravenously injected into aged female SCH mice via the tail vein on day 0 and day 10. The levels of thyroid hormone and blood lipids as well as cardiac function, serum immunological indexes, and apoptosis of thyroid cells were then analyzed on day 5, 10, 15, and 20; meanwhile, the quantity of Th1, Th2, Th17, and Treg immune cells in peripheral blood was evaluated before and on day 20 post-injection. Our study demonstrated that after hAMSC transplantation, the thyroid functions, blood lipid levels, and heart function indexes of age-related SCH (AR-SCH) mice were significantly improved. Consistent with this, Th1 and Treg cells increased significantly, while Th2 and Th17 cells decreased in peripheral blood. Apoptosis was also suppressed in the thyroid cells. In summary, hAMSC delivery can potentially be a safe and effective therapy for treating SCH in the elderly, improving related complications by immunomodulatory and apoptosis inhibition.

Enzymatic DNA repairing amplification-powered construction of an Au nanoparticle-based nanosensor for single-molecule monitoring of cytosine deaminase activity in cancer cells - Wen-jing Liu; Rui Song; Xiao-ran Zou; Dong-ling Li; Qinfeng Xu; Chun-yang Zhang (Analytica Chimica Acta, 2023)

Meta-analytic and experimental evidence that warmer climate leads to shift from advanced to delayed spring phenology - Jing Guo; Qimei Ma; Hanfeng Xu; Yue Luo; Dashan He; Fucheng Wang; Jiasheng Wu; Yongshuo H. Fu; Jianquan Liu; Rui Zhang; Lei Chen (Agricultural and Forest Meteorology, 2023)

The evolution of insecticide resistance in the white backed planthopper Sogatella furcifera (Horvath) of China in the period 2014–2022 - Ya-Ting Liu; Xin-Yu Song; Bin Zeng; Wen-Jing Zhang; Xing-Yu Chen; Ze-Rui Feng; Hua-Yang Yu; Cong-Fen Gao; Shun-Fan Wu (Crop Protection, 2023)

Dynamic simulation and control strategy exploration of the unsafe behavior of coal mine employees - Wanzhen Li; Lujie Zhou; Jian Hao; Kai Yu; Jing Chen; Pingping Liu; Rui Feng (Resources Policy, 2023)

Analysis of the contribution of land consolidation to sustainable poverty alleviation under various natural conditions - Hanbing Li; Xiaobin Jin; Barbara Prack McCormick; Pablo Tittonell; Jing Liu; Bo Han; Rui Sun; Yinkang Zhou (Land Use Policy, 2023)

QSPR models for sublimation enthalpy of energetic compounds - Rui Liu; Yuechuan Tang; Jie Tian; Jing Huang; Chaoyang Zhang; Linyuan Wang; Jian Liu (Chemical Engineering Journal, 2023)

Lactiplantibacillus plantarum Regulated Intestinal Microbial Community and Cytokines to Inhibit Salmonella typhimurium Infection - Rui-Han Liu; An-Qi Sun; Ye Liao; Zheng-Xu Tang; Shi-Han Zhang; Xin Shan; Jing-Tao Hu (Probiotics and Antimicrobial Proteins, 2023)

Hong Kong–Zhuhai–Macao Bridge deformation monitoring using PPP-RTK with multipath correction method - Rui Gao; Zhizhao Liu; Robert Odolinski; Qiang Jing; Jiantong Zhang; Hua Zhang; Baocheng Zhang (GPS Solutions, 2023)

An epoxide-based covalent sensor to detect cardiac proteome aggregation in a cardio-oncology model - Hao Jin; Di Shen; Biao Jing; Zhenduo Zhang; Zhiming Wang; Rui Sun; Huaiyue Zhang; Jialu Sun; Haochen Lyu; Yu Liu; Lili Wang (Analytica Chimica Acta, 2023)

Uncertainty in China's food self-sufficiency: A dynamic system assessment - Xinyuan Liang; Xiaobin Jin; Xiaoxiao Xu; Hefeng Chen; Jing Liu; Xuhong Yang; Weiyi Xu; Rui Sun; Bo Han; Yinkang Zhou (Sustainable Production and Consumption, 2023)

A mega study of antibiotics contamination in Eastern aquatic ecosystems of China: occurrence, interphase transfer processes, ecotoxicological risks, and source modeling - Abdul Qadeer; Guo Rui; Liu Yaqing; Dai Ran; Chengyou Liu; Dong Jing; Muhammad Anis; Mengyang Liu; Shuhang Wang; Xia Jiang; Xingru Zhao (Journal of Hazardous Materials, 2023)

Characterizing VOCs emissions of five packaging and printing enterprises in China and the emission reduction potential of this industry - Guiying You; Hefan Liu; Rui Sun; Zengxin Jin; Jing Li; Xiaoling Zhou; Sihua Lu; Shaodong Xie (Journal of Cleaner Production, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Transcriptional investigation of the toxic mechanisms of perfluorooctane sulfonate in rats based on an RNA-Seq approach - Tianrun Wang; Xuying Zhao; Tianze Liu; Jiguang Zhang; Jing Qiu; Mei Li; Rui Weng (Chemosphere, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Application of Clostridium butyricum, Rummeliibacillus suwonensis, and Issatchenkia orientalis for Nongxiangxing baijiu fermentation: Improves the microbial communities and flavor of upper fermented grain - Tongwei Guan; Xiaotian Wu; Rui Hou; Lei Tian; Qiao Huang; Fan Zhao; Ying Liu; Shirong Jiao; Shuangquan Xiang; Jiaxu Zhang; Dong Li; Jing Luo; et al. (Food Research International, 2023)

Benzene abatement catalyzed by Ceria-Supported platinum nanoparticles and single atoms - Jing Liu; Xue Fang; Daoqing Liu; Xiaolei Hu; Tian Qin; Junxiao Chen; Rui Liu; Dongrun Xu; Weiye Qu; Yangyang Dong; Liwei Chen; Zhen Ma; et al. (Chemical Engineering Journal, 2023)

A Novel D-π-A Type Fluorescent Probe for Cu2+ Based on Styryl-Pyridinium Salts Conjugating Di-(2-picolyl)amine (DPA) Units - Rui Cao; Mengyu Zhang; Wen Tang; Jing Wu; Meixiang Wang; Xiaoxiao Niu; Zhaodi Liu; Fuying Hao; Huajie Xu (Journal of Fluorescence, 2023)

The tectono-magmatic formation and submarine geohazards of the Japan Sea: Constraints from in-situ trace elements and Sr isotopes of plagioclase and clinopyroxene - Shuang-Shuang Chen; Jing Chen; Qiuming Cheng; Rui Gao; Jia-Qi Liu (Marine and Petroleum Geology, 2023)

Blending n-octanol with biodiesel for more efficient and cleaner combustion in diesel engines: A modeling study - Jing Li; Yifei Liang; Shuo Wang; Shaohua Wu; Wenming Yang; Rui Liu (Journal of Cleaner Production, 2023)

Deciphering riverine dissolved organic matter biodegradation: Evidence from three-dimensional fluorescence - Rong Xu; Jing Zhang; Jianwei Li; Rui Liu; Maofei Ni; Guangneng Zeng (Journal of Environmental Chemical Engineering, 2023)

Mechanistic insights into dissolved organic matter-driven protistan and bacterial community dynamics influenced by vegetation restoration - Zhang-mu Jing; Qing-qian Li; Yan-jie Wei; Bin Dong; Peng Yuan; Rui-xia Liu; Hong-jie Gao (Environmental Research, 2023)

A testis-specific gene doublesex is involved in spermatogenesis and early sex differentiation of the Chinese mitten crab Eriocheir sinensis - Long Wang; Zhi-Qiang Liu; Ke-Yi Ma; Jing-Rui Tao; Xiang Fang; Gao-Feng Qiu (Aquaculture, 2023)

Examining moisture contribution for precipitation in response to climate change and anthropogenic factors in Hengduan Mountain Region, China - Xingxing Zhang; Zhaofei Liu; Yubo Liu; Liguang Jiang; Rui wang; Hou Jiang; Jing Li; Qiuhong Tang; Zhijun Yao (Journal of Hydrology, 2023)

Photo-assisted thermal catalysis for methanol synthesis from methane oxidation on Cu-MOR/g-C3N4 - Yan-Qun Chen; Rui-Xin Zhang; Miao Ren; Ya-Xin Jin; Wen-Jing Wang; Jia-Yao Feng; Zhi-Hua Gao; Zhi-Feng Yan; Yi-Ming Liu; Wei Huang; Lei Liu; Zhi-Jun Zuo (Fuel, 2023)

Wide-Scope Multi-residue analysis of pesticides in beef by gas chromatography coupled with quadrupole Orbitrap mass spectrometry - Xu Pang; Jing Qiu; Zhaoyang Zhang; Pi Li; Jiangtao Xing; Xin Su; Guiqiao Liu; Changyuan Yu; Rui Weng (Food Chemistry, 2023)

An injectable and rapidly degraded carboxymethyl chitosan/polyethylene glycol hydrogel for postoperative antiadhesion - Meiyue Wang; Sen Lin; Mengzhe Liu; Jing Jiao; Hongyan Mi; Jingjing Sun; Yiming Liu; Ruiying Guo; Sirui Liu; Haojie Fu; Yanyu Yang; Rui Li (Chemical Engineering Journal, 2023)

A novel reduced graphene oxide/polypyrrole conductive ceramic membrane enhanced electric field membrane bioreactor: Mariculture wastewater treatment performance and membrane fouling mitigation - Rui Wang; Hong You; Zhipeng Li; Binghan Xie; Shaojie Qi; Jing Zhu; Qiqing Qin; Han Wang; Jinxu Sun; Yi Ding; Yuhong Jia; Feng Liu (Bioresource Technology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Exogenous methyl jasmonate and cytokinin antagonistically regulate lignin biosynthesis by mediating CsHCT expression in Camellia sinensis - Chun-Fang Liu; Ni Yang; Rui-Min Teng; Jing-Wen Li; Yi Chen; Zhi-Hang Hu; Tong Li; Jing Zhuang (Protoplasma, 2023)

Regulating the reaction pathway of nZVI to improve the decontamination performance through magnetic spatial confinement effect - Hai-Yuan Chi; Xiao-Xia Zhou; Min-Rong Wu; Wan-yu Shan; Jing-fu Liu; Jin-quan Wan; Bing Yan; Rui Liu (Journal of Hazardous Materials, 2023)

Long-term exposure to fine particulate matter and site-specific cancer mortality: A difference-in-differences analysis in Jiangsu province, China - Zhaoyu Fan; Yingxin Li; Jing Wei; Gongbo Chen; Rui Wang; Ruijun Xu; Tingting Liu; Ziquan Lv; Suli Huang; Hong Sun; Yuewei Liu (Environmental Research, 2023)

Managing iodine and tin based defects for efficient and stable mixed Sn-Pb perovskite solar cells - Yanjun Xing; Zhiqiang Deng; Tonghui Guo; Zequn Zhang; Qidong Tai; Rui Zhao; Jiaxing Xiong; Qiuxiang Wang; Like Huang; Xiaohui Liu; Ziyang Hu; Yuejin Zhu; et al. (Chemical Engineering Journal, 2023)

An ultra-thin chemical vapor deposited polymer interlayer to achieve highly improved stability of perovskite solar cell - Jing Zhou; Xueying Tian; Rui Chen; Weitao Chen; Xin Meng; Xinyu Guan; Jianan Wang; Sanwan Liu; Fumeng Ren; Shasha Zhang; Yiqiang Zhang; Zonghao Liu; et al. (Chemical Engineering Journal, 2023)

Parameter Study on How the Cervical Disc Degeneration Affects the Segmental Instantaneous Centre of Rotation - Hong Zhang; Dacheng Sang; Bin Zhang; Ya-Nan Ren; Xin Wang; Jing-Jing Feng; Cheng-Fei Du; Baoge Liu; Rui Zhu (Journal of Medical and Biological Engineering, 2023)

Cross-subject aesthetic preference recognition of Chinese dance posture using EEG - Jing Li; Shen-rui Wu; Xiang Zhang; Tian-jian Luo; Rui Li; Ying Zhao; Bo Liu; Hua Peng (Cognitive Neurodynamics, 2023)

Moderation device design for detecting hidden highly enriched uranium based on D-T neutron generator - Shang-Rui Jiang; Guang-Yu Shi; Si-Yuan Chen; Shi-Wei Jing; Chao Liu (Annals of Nuclear Energy, 2023)

Identification of three Streptomyces strains and their antifungal activity against the rubber anthracnose fungus Colletotrichum siamense - Jinhong Wang; Rui Wang; Jing Gao; Huanqing Liu; Wen Tang; Zhiqiang Liu; Xiaoyu Li (Journal of General Plant Pathology, 2023)

Changes in PM2.5-related health burden in China's poverty and non-poverty areas during 2000–2020: A health inequality perspective - Yan Li; Baojie Li; Hong Liao; Bing-Bing Zhou; Jing Wei; Yuxia Wang; Yuzhu Zang; Yang Yang; Rui Liu; Xiaorui Wang (Science of The Total Environment, 2023)

Gonad development and recruitment pattern of the oysters Crassostrea ariakensis and Crassostrea sikamea in a subtropical bay in China - Wei Jiang; Wen-Jing Shi; Nan-Nan Li; Wen-Kao Zhang; Li-Zhi Chen; Qi Liu; Chun-Yu Ye; Rui-Liang Fan; Wei-Min Quan (Regional Studies in Marine Science, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

The off-axis plume–ridge interaction model: Confirmation from the mineral chemistry of Cretaceous basalts of the Ontong Java Plateau - Jing Chen; Shuang-Shuang Chen; Donald B. Dingwell; Rui Gao; Jia-Qi Liu (Chemical Geology, 2023)

Rapid and massive fractionation of hemicelluloses for purifying cellulose at room temperature by tetramethylammonium hydroxide - Rui Tian; Bolang Zhu; Qiaoling Liu; Yajie Hu; Ziying Yang; Jun Rao; Yuying Wu; Baozhong Lü; Jing Bian; Feng Peng (Bioresource Technology, 2023)

Long-term exposure to ambient particulate matter and kidney function in older adults - Yingxin Li; Xueli Yuan; Jing Wei; Yuanying Sun; Wenqing Ni; Hongmin Zhang; Yan Zhang; Rui Wang; Ruijun Xu; Gongbo Chen; Yuewei Liu; Jian Xu (Atmospheric Environment, 2023)

Simultaneous measurement of multiple labile heavy metals in soils by diffusive gradients in thin film technique - Rui Chen; Jiaxing Liu; Guoyu Ding; Fumin Ren; Rongguang Shi; Jungang Lv; Jing Cheng (Journal of Soils and Sediments, 2023)

Significance of silicate liquid immiscibility for the origin of young highly evolved lithic clasts in Chang’E-5 regolith - Jing Yang; Dongyang Ju; Runlian Pang; Rui Li; Jianzhong Liu; Wei Du (Geochimica et Cosmochimica Acta, 2023)

Influence of collaborative disposal of sewage sludge in the fly ash partitioning and PM10 emission from a subcritical coal-fired boiler - Tianyu Liu; Chang Wen; Ke Zhou; Changkang Li; Youjian Zhu; Dapeng Wang; Rui Li; Zhenqi Jing (Fuel, 2023)

Breast adipose metabolites mediates the association of tetrabromobisphenol a with breast cancer: A case-control study in Chinese population - Ai Zhang; Rui Wang; Qianfeng Liu; Zhengjun Yang; Xiaohui Lin; Jing Pang; Xiaoyu Li; Dan Wang; Jiayu He; Jianping Li; Mingyue Zhang; Yue Yu; et al. (Environmental Pollution, 2023)

Facile fabrication of hierarchically porous melamine foam@COF composite for sample treatment of non-targeted food safety analysis and oil/water separation - Wei Li; Wei-Liang Jin; Hong-Xin Jiang; Rui Wang; Hao Jia; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

A High-efficiency blue-LED-excitable NIR-II-emitting MgO:Cr3+,Ni2+ phosphor for future broadband light source toward multifunctional NIR spectroscopy applications - Bo-Mei Liu; Xiao-Xuan Guo; Lu-Yu Cao; Lin Huang; Rui Zou; Zhi Zhou; Jing Wang (Chemical Engineering Journal, 2023)

Formation mechanism and metabolic pathways of photogranule in batch and continuous-flow mode under high salinity stress - Jing Zhu; Hong You; Zhipeng Li; Binghan Xie; Weirun Li; Shaojie Qi; Rui Wang; Hongying Chen; Binyu Ma; Yi Ding; Haili Tan; Feng Liu; et al. (Chemical Engineering Journal, 2023)

Rationally tailoring anion traps into electrospun nanofibers for highly efficient perrhenate/pertechnetate capture - Dingyang Chen; Zhaoli Liu; Shuying Li; Xiaofei Jing; Yuyang Tian; Wei Hu; Fengchao Cui; Rui Zhao; Guangshan Zhu (Chemical Engineering Journal, 2023)

In-situ growth of bimetallic FeCo-MOF on magnetic biochar for enhanced clearance of tetracycline and fruit preservation - Yi-Cai Jiang; Meng-Fan Luo; Zi-Nuo Niu; Si-Yuan Xu; Yue Gao; Yuan Gao; Wen-Juan Gao; Jing-Jing Luo; Rui-Lin Liu (Chemical Engineering Journal, 2023)

Positional cloning identified HvTUBULIN8 as the candidate gene for round lateral spikelet (RLS) in barley (Hordeum vulgare L.) - Dandan Qin; Gang Liu; Rui Liu; Chunchao Wang; Fuchao Xu; Qing Xu; Yu Ling; Guoqing Dong; Yanchun Peng; Shuangtao Ge; Ganggang Guo; Jing Dong; et al. (Theoretical and Applied Genetics, 2023)
Key message Map-based cloning, subcellular localization, virus-induced-gene-silencing and transcriptomic analysis reveal HvTUB8 as a candidate gene with pleiotropic effects on barley spike and leaf development via ethylene and chlorophyll metabolism. Abstract Barley lateral spikelet morphology and grain shape play key roles in grain physical quality and yield. Several genes and QTLs for these traits have been cloned or fine mapped previously. Here, we report the phenotypic and genotypic analysis of a barley mutant with round lateral spikelet (rls) from cv. Edamai 934. rls had round lateral spikelet, short but round grain, shortened awn, thick glume and dark green leaves. Histocytologic and ultrastructural analysis revealed that the difference of grain shape of rls was caused by change of cell arrangement in glume, and the dark leaf color resulted from enlarged chloroplast. HvTUBULIN8 ( HvTUB8 ) was identified as the candidate gene for rls by combination of RNA-Seq, map-based-cloning, virus-induced-gene-silencing (VIGS) and protein subcellular location. A single G-A substitution at the third exon of HvTUB8 resulted in change of Cysteine 354 to tyrosine. Furthermore, the mutant isoform Hvtub8 could be detected in both nucleus and cytoplasm, whereas the wild-type protein was only in cytoplasm and granular organelles of wheat protoplasts. Being consistent with the rare phenotype, the “A” allele of HvTUB8 was only detected in rls , but not in a worldwide barley germplasm panel with 400 accessions. VIGS confirmed that HvTUB8 was essential to maintain spike integrity. RNA-Seq results suggested that HvTUB8 may control spike morphogenesis via ethylene homeostasis and signaling, and control leaf color through chlorophyll metabolism. Collectively, our results support HvTUB8 as a candidate gene for barley spike and leaf morphology and provide insight of a novel mechanism of it in barley development.

Azospirillum Endophyticum sp. nov., an Endophyte of Paris Polyphylla Smith var. Yunnanensis - Peng-Chao Zhan; Rui-Feng Mao; Cong-Jian Li; Zhen Zhang; Jing-Ran Liu; Mei Tang; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2023)

Typhoon-Resistant Performance Assessment of Coastal Rural Residential Keel Brick Walls Reinforced with High Ductility Concrete - Qiang Li; Jun Zhang; Rui Wang; Jing Liu; Ping Li (Journal of Marine Science and Engineering, 2022)
The keel brick wall belongs to the rural residential exterior wall unique to the southeast coastal region of China. The wooden keel inside the wall and the external tie members can improve the stability of the whole wall. However, due to the age of construction, the wooden keel inside the existing residential keel brick walls has basically rotted and lost the tie with the external members, which seriously reduces the stability of the whole wall. Moreover, the collapse of keel brick walls caused by typhoons has become more and more frequent in recent years, seriously endangering the lives and properties of residents. Therefore, it is necessary to carry out reinforcement and repair for the existing residential buildings with keel brick walls. In this paper, the keel brick walls of rural houses in Ningbo area were taken as the research object, a framework for evaluating the performance of keel brick walls against typhoons was established, tests on the lateral force resistance of keel brick walls reinforced with high ductility concrete and mortar were carried out. With the help of typhoon full-track simulation and wind field simulation technology, the 600-year near-surface typhoon wind speeds affecting Ningbo area were obtained. A joint probability distribution model of multi-directional extreme wind speed was constructed using t-Copula function to determine the mixed wind climate of Ningbo area. The extreme wind loads that keel brick walls can withstand under four types of reinforcement were finally given. The results show that the high ductility concrete reinforcement has great advantages over mortar reinforcement and avoids brittle damage of the masonry structure. The keel brick walls reinforced with single-sided mortar can withstand wind loads of a 3-year return period, the keel brick walls reinforced with single-sided high ductile concrete can withstand extreme wind loads of a 110-year return period, while the keel brick walls reinforced with double-sided mortar as well as double-sided high ductile concrete can withstand extreme wind loads of well over a 110-year return period.

Novel and sustainable carboxylation of terminal alkynes and CO2 to alkynyl carboxylic acids using triazolium ionic liquid-modified PMO-supported transition metal acetylacetonate as effective cooperative catalysts - Jing-Rui Li; Chen Chen; Xiao-Bing Liu; Yu-Lin Hu (Environmental Science and Pollution Research, 2022)

Characterization of a Hyaluronidase-Producing Bacillus sp. CQMU-D Isolated from Soil - Lu Wang; Qianqian Liu; Rui Hao; Jing Xiong; Junxing Li; Yanan Guo; Lu He; Zeng Tu (Current Microbiology, 2022)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Nutrient Reabsorption Mechanism Adapted to Low Phosphorus in Wild and Cultivated Soybean Varieties - Wenyue Shen; Rui Guo; Yaxuan Zhao; Danping Liu; Jing Chen; Ningning Miao; Shujuan Gao; Tao Zhang; Lianxuan Shi (Journal of Plant Growth Regulation, 2022)

miR-517b-3p promotes the progression of portal vein tumor thrombus via activating Wnt/β-catenin signaling pathway in hepatocellular carcinoma - Rui-Sheng Ke; Kun-Zhai Huang; De-sheng Bao; Jing-Rui Yang; Hua-xiang Wang; Li-Zhi Lv; Yi Jiang; Zhao-Hui Liu; Fu-Xing Zhang (Molecular Biology Reports, 2022)

Preparing porous Cu/Pd electrode on nickel foam using hydrogen bubbles dynamic template for high-efficiency and high-stability removal of nitrate from water - Jialu Shi; Ya Gao; Daoru Liu; Zhanhui Shen; Jing Fan; Yating Yu; Meihui Bao; Panpan Li; Rui Yao (Environmental Science and Pollution Research, 2022)

The effects of dietary fermented wheat bran polysaccharides on mucosal and serum immune parameters, hepatopancreas antioxidant indicators, and immune-related gene expression of common carp (Cyprinus carpio) juveniles - Rui-Fang Wang; Yuan Wang; Jun Zhang; Mei-Qi Weng; Yu-Hui Liu; Qiu-Yan Cheng; Min Song; Yan-Ping Yang; Xiao-Ping An; Jing-Wei Qi (Aquaculture International, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Early changes to the extracellular space in the hippocampus under simulated microgravity conditions - Yajuan Gao; Hongbin Han; Jichen Du; Qingyuan He; Yanxing Jia; Junhao Yan; Hui Dai; Bin Cui; Jing Yang; Xunbin Wei; Liu Yang; Rui Wang; et al. (Science China Life Sciences, 2022)

Identification and Expression Analysis of the SBP-box Gene Family Related to Abiotic Stress in Tea Plant (Camellia sinensis (L.) O. Kuntze) - Rui-Min Teng; Yong-Xin Wang; Hui Li; Hao Liu; Yu Wang; Jing Zhuang (Plant Molecular Biology Reporter, 2022)

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Molecular cloning and functional characterization of two squalene synthase genes in Atractylodes lancea - Junxian Wu; Rui Xu; Jimei Lu; Weiwei Liu; Hanwen Yu; Mengli Liu; Jing Li; Minzhen Yin; Huasheng Peng; Liangping Zha (Planta, 2022)

Peripheral Administration of an Opioid Peptide Analog Ameliorates Morphine-Produced Hyperalgesia in a Spared Nerve Injury Model - Yuan Wang; Meng-tao Ma; Jing Wang; Chao-zhen-yi Han; Kai Li; Qiao-min Ru; Na Li; Xin Liu; Rui Wang (International Journal of Peptide Research and Therapeutics, 2022)

Putative role of uncoupling proteins in mitochondria-nucleus communications and DNA damage response - Yahan Niu; Chang Liu; Rui Zhang; Ying Jing; Donghai Li (Journal of Biosciences, 2021)

A concise review of the brown seaweed Sargassum thunbergii — a knowledge base to inform large-scale cultivation efforts - Fu-Li Liu; Jing-Jing Li; Zhou-Rui Liang; Quan-Sheng Zhang; Feng-Juan Zhao; Alexander Jueterbock; Alan T. Critchley; Stephen L. Morrell; Jorge Assis; Yong-Zheng Tang; Zi-Min Hu (Journal of Applied Phycology, 2021)

Two new diterpenoids with their antiproliferative activities from the supercritical fluid extraction of Croton crassifolius root - Chao Liu; Rui-rui Zhang; Qing-lin Niu; Jing Zhang; Mu-xuan Wang; Na-na Meng; Qing Wang; Jin-yue Sun; Wen-liang Wang (Natural Product Research, 2021)

Characteristics of Ichthyoplankton Communities and Their Relationship With Environmental Factors Above the Ninety East Ridge, Eastern Indian Ocean - Liyan Zhang; Jing Zhang; Shigang Liu; Rui Wang; Jiali Xiang; Xing Miao; Ran Zhang; Puqing Song; Longshan Lin (Frontiers in Marine Science, 2021)
The Ninety East Ridge is a submarine north–south oriented volcanic ridge in the eastern Indian Ocean. Surface-layer ichthyoplankton collected in this area from September to October were identified by combined morphological and molecular (DNA barcoding) techniques, and their species composition, diversity, and abundance, and correlations with environmental variables were described. Collections comprised 109 larvae and 507 eggs, which were identified to 37 taxa in 7 orders, 20 families, and 27 genera, and were dominated by the order Perciformes and species Vinciguerria sp., Oxyporhamphus micropterus , and Decapterus macarellus . Species abundances at each station and of each species were relatively low, suggesting that this area or the time of sampling were not of major importance for fish spawning. Waters above Ninety East Ridge had lower species diversity but higher species richness than waters further offshore. A generalized additive model revealed that high abundance of ichthyoplanktonic taxa occurred in areas with low sea surface height and high sea surface salinity, temperature, and chlorophyll a concentration. Of these, sea surface height was most correlated with ichthyoplankton abundance. We provided baseline data on surface-dwelling ichthyoplankton communities in this area to aid in development of pelagic fishery resources in waters around the Ninety East Ridge.

Chronic Exposure to Hypoxia Inhibits Myelinogenesis and Causes Motor Coordination Deficits in Adult Mice - Lin Chen; Shu-Yu Ren; Rui-Xue Li; Kun Liu; Jing-Fei Chen; Yu-Jian Yang; Yong-Bin Deng; Han-Zhi Wang; Lan Xiao; Feng Mei; Fei Wang (Neuroscience Bulletin, 2021)
Exposure to chronic hypoxia is considered to be a risk factor for deficits in brain function in adults, but the underlying mechanisms remain largely unknown. Since active myelinogenesis persists in the adult central nervous system, here we aimed to investigate the impact of chronic hypoxia on myelination and the related functional consequences in adult mice. Using a transgenic approach to label newly-generated myelin sheaths ( NG2-CreER TM ; Tau-mGFP ), we found that myelinogenesis was highly active in most brain regions, such as the motor cortex and corpus callosum. After exposure to hypoxia (10% oxygen) 12 h per day for 4 weeks, myelinogenesis was largely inhibited in the 4-month old brain and the mice displayed motor coordination deficits revealed by the beam-walking test. To determine the relationship between the inhibited myelination and functional impairment, we induced oligodendroglia-specific deletion of the transcription factor Olig2 by tamoxifen ( NG2-CreER TM ; Tau-mGFP; Olig2 fl/fl ) in adult mice to mimic the decreased myelinogenesis caused by hypoxia. The deletion of Olig2 inhibited myelinogenesis and consequently impaired motor coordination, suggesting that myelinogenesis is required for motor function in adult mice. To understand whether enhancing myelination could protect brain functions against hypoxia, we treated hypoxic mice with the myelination-enhancing drug-clemastine, which resulted in enhanced myelogenesis and improved motor coordination. Taken together, our data indicate that chronic hypoxia inhibits myelinogenesis and causes functional deficits in the brain and that enhancing myelinogenesis protects brain functions against hypoxia-related deficits.

Analytical solution of grouting fracturing height for the post-grouted bored piles using the Herschel–Bulkley model with time-varying viscosity - Gan Nan; Hai-ming Liu; Yong-mei Peng; Rui Liang; Hong-tao Xie; Jing Cao (Arabian Journal of Geosciences, 2021)

Dicer Deletion in Astrocytes Inhibits Oligodendroglial Differentiation and Myelination - Kun Liu; Bin Yu; Jing-Fei Chen; Rui-Xue Li; Lin Chen; Shu-Yu Ren; Fei Wang; Feng Mei; Lan Xiao (Neuroscience Bulletin, 2021)
Increasing evidence has shown that astrocytes are implicated in regulating oligodendrocyte myelination, but the underlying mechanisms remain largely unknown. To understand whether microRNAs in astrocytes function in regulating oligodendroglial differentiation and myelination in the developing and adult CNS, we generated inducible astrocyte-specific Dicer conditional knockout mice (hGFAP-CreERT; Dicer fl/fl). By using a reporter mouse line (mT/mG), we confirmed that hGFAP-CreERT drives an efficient and astrocyte-specific recombination in the developing CNS, upon tamoxifen treatment from postnatal day 3 (P3) to P7. The Dicer deletion in astrocytes resulted in inhibited oligodendroglial differentiation and myelination in the developing CNS of Dicer cKO mice at P10 and P14, and did not alter the densities of neurons or axons, indicating that Dicer in astrocytes is required for oligodendrocyte myelination. Consequently, the Dicer deletion in astrocytes at P3 resulted in impaired spatial memory and motor coordination at the age of 9 weeks. To understand whether Dicer in astrocytes is also required for remyelination, we induced Dicer deletion in 3-month-old mice and then injected lysolecithin into the corpus callosum to induce demyelination. The Dicer deletion in astrocytes blocked remyelination in the corpus callosum 14 days after induced demyelination. Together, our results indicate that Dicer in astrocytes is required for oligodendroglia myelination in both the developing and adult CNS.

Swi6B , an alternative splicing isoform of Swi6, mediates the cell wall integrity of Ganoderma lucidum - Lingdan Lian; Guang Zhang; Jing Zhu; Yunxiao Wang; Lingshuai Wang; Rui Liu; Liang Shi; Ang Ren; Mingwen Zhao (Environmental Microbiology, 2021)
Summary The cell wall integrity (CWI) signaling activates the transcription factor Swi6 through a MAPK signaling cascade in response to cell wall stresses. In this study, we observed two different mRNA variants of swi6 ( GlSwi6A and GlSwi6B ) existed, due to alternative splicing. Besides, the expression level of GlSwi6B was higher than that of the GlSwi6A mRNA variant. The co‐silencing of GlSwi6A and GlSwi6B was more sensitive to cell wall stress compared with WT, resulting in a decrease of 78% and 76% in chitin and β‐1,3‐ d ‐glucan content respectively. However, only the overexpression of GlSwi6B decreased the sensitivity to cell wall stress and increased the content of chitin and β‐1,3‐ d ‐glucan compared with the WT strain. Furthermore, Y1H, EMSA and BLI assays revealed that the GlSwi6B could bind to the promoters of chitin and glucan synthesis genes (GL24454 and GL18134). However, the binding phenome has not been observed in the isoform GlSwi6A. Taken together, our results found two different transcripts generated from Swi6 , in which the alternative splice isoform of GlSwi6B participates in regulating the CWI of G . lucidum . This study provides the first insight into the alternative splicing isoform of GlSwi6B in the regulation of CWI signaling in fungi.

Seasonal variations of water quality response to land use metrics at multi-spatial scales in the Yangtze River basin - Jiahui Xu; Rui Liu; Maofei Ni; Jing Zhang; Qin Ji; Zuolin Xiao (Environmental Science and Pollution Research, 2021)

Overexpression of CpSIZ1, a SIZ/PIAS-Type SUMO E3 Ligase from Wintersweet (Chimonanthus praecox), Delays Flowering, Accelerates Leaf Senescence and Enhances Cold Tolerance in Arabidopsis - Rui Li; Jing Ma; Huamin Liu; Xia Wang; Jing Li; Zhineng Li; Mingyang Li; Shunzhao Sui; Daofeng Liu (Plant Molecular Biology Reporter, 2021)

Characterization of a novel marine aerobic denitrifier Vibrio spp. AD2 for efficient nitrate reduction without nitrite accumulation - Jilong Ren; Hongjing Ma; Ying Liu; Yunjie Ruan; Chenzheng Wei; Jing Song; Yinghai Wu; Rui Han (Environmental Science and Pollution Research, 2021)

Protective effect of Lycium barbarum polysaccharide on di-(2-ethylhexyl) phthalate-induced toxicity in rat liver - Rui-jing Liu; Yong-jian He; Huan Liu; Dong-dong Zheng; Shao-wen Huang; Chun-hong Liu (Environmental Science and Pollution Research, 2021)

Optimizing Protein-Glutaminase Expression in Bacillus subtilis - Xiaoying Ouyang; Yingjie Liu; Ruidan Qu; Min Tian; Ting Yang; Rui Zhu; Hongliang Gao; Mingfei Jin; Jing Huang (Current Microbiology, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Diversity-oriented synthesis and antifungal activities of novel pimprinine derivative bearing a 1,3,4-oxadiazole-5-thioether moiety - Zi-Long Song; Yun Zhu; Jing-Rui Liu; Shu-Ke Guo; Yu-Cheng Gu; Xinya Han; Hong-Qiang Dong; Qi Sun; Wei-Hua Zhang; Ming-Zhi Zhang (Molecular Diversity, 2021)

Vertical influence of temperature and precipitation on snow cover variability in the Yarlung Zangbo River basin, China - Chunguang Ban; Zongxue Xu; Depeng Zuo; Xiaowan Liu; Rui Zhang; Jing Wang (International Journal of Climatology, 2021)
Seasonal snow cover in mountainous areas is a key source of water for downstream regions. The snow cover area (SCA) in the Northern Hemisphere has significantly decreased during the past decades in response to global warming. Therefore, it is necessary to investigate the primary factors controlling the spatiotemporal variabilities in the SCA in high altitude regions. In this study, based on remote sensing data of SCA, temperature, and precipitation in the Yarlung Zangbo River basin, Pearson's correlation analysis was used to identify the relative importance of temperature and precipitation on the SCA variability with altitude. The results showed that temperature played a more dominant role for the SCA than precipitation at all elevation during the period 2001–2017; three threshold altitudes at high, moderate, and low elevation were identified, and these threshold altitudes are dynamic and vary with time; the threshold altitude at high elevation was 5,925 ± 125 m, below which temperature (precipitation) was negatively (positively) correlated and above which temperature (precipitation) was positively (negatively) correlated with the SCA; the threshold altitude at moderate elevation was 3,200 ± 300 m, below which temperature (precipitation) was positively (negatively) correlated and above which temperature (precipitation) was negatively (positively) correlated with the SCA; the threshold altitude in low elevation regions was 2,100 ± 200 m. This study sheds light on the dominant climatic control factors on the variability in SCA in high altitude regions. These results have major implications for SCA and water resources availability under future climate change.

Nitric oxide regulates ganoderic acid biosynthesis by the S‐nitrosylation of aconitase under heat stress in Ganoderma lucidum - Rui Liu; Ting Zhu; Tao Yang; Zhengyan Yang; Ang Ren; Liang Shi; Jing Zhu; Hanshou Yu; Mingwen Zhao (Environmental Microbiology, 2021)
Summary Nitric oxide (NO) is an important signalling molecule in stress response of organisms. We previously reported that NO decreases heat stress (HS)‐induced ganoderic acid (GA) accumulation in Ganoderma lucidum . To explore the mechanisms by which NO modulates GA biosynthesis under HS, the effect of NO on the reactive oxygen species (ROS) content was examined. The results showed that NO decreased the production of mitochondrial ROS (mitROS) by 60% under HS. Further research revealed that NO reduced the mitROS content by inhibiting aconitase (Acon) activity. The GA content in Acon‐silenced (Aconi) strains treated with NO donor did not differ significantly from that in untreated Aconi strains. To study the mechanism by which Acon activity is inhibited, the S‐nitrosylation level of Acon was determined. Biotin‐switch technology and mass spectrometry analysis were used to show that Acon is S‐nitrosylated at the Cys‐594 amino acid residue. Substitution of Cys‐594 with a Ser, which cannot be S‐nitrosylated, abolished the responsiveness of Acon to the NO‐induced reduction in its enzymatic activity. These findings demonstrate that NO inhibits Acon activity through S‐nitrosylation at Cys‐594. In summary, these findings describe mechanism by which NO regulates GA biosynthesis via S‐nitrosylation of Acon under HS condition in G . lucidum .

Identification and expression analysis of caffeoyl-coenzyme A O-methyltransferase family genes related to lignin biosynthesis in tea plant (Camellia sinensis) - Shi-Jia Lin; Ya-Zhuo Yang; Rui-Min Teng; Hao Liu; Hui Li; Jing Zhuang (Protoplasma, 2021)

Effects of shading on lignin biosynthesis in the leaf of tea plant (Camellia sinensis (L.) O. Kuntze) - Rui-Min Teng; Yong-Xin Wang; Hui Li; Shi-Jia Lin; Hao Liu; Jing Zhuang (Molecular Genetics and Genomics, 2021)

Comparison of rapid freezing versus vitrification for human sperm cryopreservation using sucrose in closed straw systems - Huanhuan Hu; Guojie Ji; Xiaowei Shi; Rui Liu; Jing Zhang; Han Zhang; Xiaozheng Yuan; Guoyi Zhang; Wenzheng Yuan; Mingwen Li (Cell and Tissue Banking, 2020)

Ultrafiltration and microfiltration membrane performance, cleaning, and flux recovery for microalgal harvesting - Rui Liu; Lan Wang; Li Yang; Qingling Liu; Yunxiao Gao; Jing Ye; Jingrong Xiao; Qiang Hu; Xuezhi Zhang (Journal of Applied Phycology, 2020)

Mechanical characteristics of soil-rock mixtures containing macropore structure based on 3D modeling technology - Yong Liu; Shao-rui Sun; Ji-hong Wei; Jing-lei Song; Yong-xiang Yu; Wei He; Ji-xing Zhang (Journal of Mountain Science, 2020)

Enhancement of the activity of Cu/TiO2 catalyst by Eu modification for selective catalytic reduction of NOx with NH3 - Yuan-zhen Liu; Qi-yan Xu; Rui-tang Guo; Chao-peng Duan; Gui-lin Wu; Yu-fang Miao; Jing-wen Gu (Environmental Science and Pollution Research, 2020)

Mouse adaptation of the H9N2 avian influenza virus causes the downregulation of genes related to innate immune responses and ubiquitin-mediated proteolysis in mice - Jing Guo; Xinxin Gao; Baotao Liu; Yubao Li; Wenqiang Liu; Jianbiao Lu; Cheng Liu; Rui Xue; Xuyong Li (Medical Microbiology and Immunology, 2020)

Tracing solute sources and carbon dynamics under various hydrological conditions in a karst river in southwestern China - Jing Liu; Bo Chen; Zhu-Yan Xu; Yuan Wei; Zhi-Hua Su; Rui Yang; Yong-Xue Ji; Xiao-Dan Wang; Li-Li Zhang; Ning An; Fei Yang (Environmental Science and Pollution Research, 2020)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

Comprehensive assessment of Coupled Model Intercomparison Project Phase 5 global climate models using observed temperature and precipitation over mainland Southeast Asia - Jing Li; Zhaofei Liu; Zhijun Yao; Rui Wang (International Journal of Climatology, 2019)
In this study, the performances of 31 global climate models (GCMs) from Coupled Model Intercomparison Project Phase 5 (CMIP5) were evaluated using observed temperature and precipitation data sets for mainland Southeast Asia (MSA). In addition, the technique for order preference by similarity to ideal solution model (TOPSIS), which is an effective multi‐objective decision method and has been widely applied in systems engineering, was used to comprehensively evaluate the GCMs on a regional scale. The meteorological variables employed included monthly mean, maximum, and minimum air temperature series and annual/seasonal precipitation during the period 1961–2004. Results showed the overall C i values ranged from 0.56 to 0.80. Overall, ACCESS1.0, HadGEM2‐A, HadGEM2‐CC, and CESM1 (BGC) performed better than the other models with respect to air temperature and precipitation over MSA. For meteorological variables, the C i of extreme temperature by GCMs was 0.65 and higher than mean temperature at 0.61. The performance of GCMs in simulating precipitation during wet season was superior to that for annual and dry season precipitation. With respect to evaluation indicators, most of the GCMs assessed in this study failed to capture observed mean annual air temperature and annual precipitation (they underestimated annual air temperature and overestimated mean annual precipitation). When evaluating the performance of the GCMs with respect to reproducing individual climatic variables, the use of various statistical evaluation criteria provided inconsistent results. These results demonstrate the need to consider the influence of different statistical eigenvalues and to employ multiple indicators when possible to enable a comprehensive evaluation of GCMs. The results of this study provide useful information for climate change, water resource, and agricultural management research in MSA.

The relief effects of organic acids on Scirpus triqueter L. under pyrene–lead stress - Xinying Zhang; Jing Chen; Xiaoyan Liu; Xueping Chen; Lu Liu; Yinghu Niu; Rui Wang (Environmental Science and Pollution Research, 2019)

Spatial distribution, source identification, and potential risk assessment of toxic contaminants in surface waters from Yulin, China - Jing Liu; Yongjun Liu; Aining Zhang; Yu Liu; Ying Zhu; Ming Guo; Rui Zhang (Environmental Monitoring and Assessment, 2019)

Transcriptome sequencing to reveal the genetic regulation of leaf margin variation at early stage in birch - Xiuyan Bian; Chang Qu; Manman Zhang; Yidi Li; Rui Han; Jing Jiang; Guifeng Liu (Tree Genetics & Genomes, 2019)

Gut microbiota in patients after surgical treatment for colorectal cancer - Ye Jin; Yang Liu; Lei Zhao; Fuya Zhao; Jing Feng; Shengda Li; Huinan Chen; Jiayu Sun; Biqiang Zhu; Rui Geng; Yunwei Wei (Environmental Microbiology, 2019)
Summary Colorectal cancer (CRC) is a common disease worldwide that is strongly associated with the gut microbiota. However, little is known regarding the gut microbiota after surgical treatment. 16S rRNA gene sequencing was used to evaluate differences in gut microbiota among colorectal adenoma patients, CRC patients, CRC postoperative patients and healthy controls by comparing gut microbiota diversity, overall composition and taxonomic signature abundance. The gut microbiota of CRC patients, adenoma patients and healthy controls developed in accordance with the adenoma‐carcinoma sequence, with impressive shifts in the gut microbiota before or during the development of CRC. The gut microbiota of postoperative patients and CRC patients differed significantly. Subdividing CRC postoperative patients according to the presence or absence of newly developed adenoma which based on the colonoscopy findings revealed that the gut microbiota of newly developed adenoma patients differed significantly from that of clean intestine patients and was more similar to the gut microbiota of carcinoma patients than to the gut microbiota of healthy controls. The alterations of the gut microbiota between the two groups of postoperative patients corresponded to CRC prognosis. More importantly, we used the different gut microbiota as biomarkers to distinguish postoperative patients with or without newly developed adenoma, achieving an AUC value of 0.72. These insights on the changes in the gut microbiota of CRC patients after surgical treatment may allow the use of the microbiota as non‐invasive biomarkers for the diagnosis of newly developed adenomas and to help prevent cancer recurrence in postoperative patients.

Postprandial change in glucose metabolism at the molecular level in the adipose tissue of omnivorous GIFT Oreochromis niloticus - Jing-Yun Feng; Qin-Qin Liu; Hang-Zhong Xu; Rui-Hong Chen; Li Luo; Shi-Mei Lin; Yong-Jun Chen; De-Shou Wang (Fisheries Science, 2019)

Acupuncture Prevents the Impairment of Hippocampal LTP Through β1-AR in Vascular Dementia Rats - Ling-Yong Xiao; Xue-Rui Wang; Jing-Wen Yang; Yang Ye; Wen Zhu; Yan Cao; Si-Ming Ma; Cun-Zhi Liu (Molecular Neurobiology, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

RNA Sequence Analysis of Cassava Varieties with High-Starch Content Using De Novo Assembly - Ya-Jing Guo; Xing-Lu Luo; Mao-Gui Wei; Zhao-Liang Liu; Wu-Jing Fan; Rui-Ning Zhai; Yan-Mei Zhu (Journal of Plant Growth Regulation, 2018)

Development of EST-SSR markers derived from transcriptome of Saccharina japonica and their application in genetic diversity analysis - Jing Zhang; Tao Liu; Fengping Rui (Journal of Applied Phycology, 2018)

Comparative growth increments of gladius surface and cross-sections to estimate Sthenoteuthis oualaniensis age - Xue Feng Wang; Bi Lin Liu; Jian Hua Li; Rui Jiang; Jing Yuan Lin; Teng Li (Marine Biology, 2018)

Ursolic acid, a potential anticancer compound for breast cancer therapy - Ran Yin; Tong Li; Jing Xin Tian; Pan Xi; Rui Hai Liu (Critical Reviews in Food Science and Nutrition, 2018)

Expression of BpIAA10 from Betula platyphylla (birch) is differentially regulated by different hormones and light intensities - Wendi Xu; Rui Han; Sijia Xu; Jing Jiang; Guifeng Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Association of ACYP2 and TSPYL6 Genetic Polymorphisms with Risk of Ischemic Stroke in Han Chinese Population - Yiqian Liang; Rui Zhang; Shuo Zhang; Guofa Ji; Puyu Shi; Tian Yang; Feng Liu; Jing Feng; Chunqi Li; Dangshe Guo; Mingwei Chen (Molecular Neurobiology, 2017)

Efficacy and safety of probiotic-supplemented triple therapy for eradication of Helicobacter pylori in children: a systematic review and network meta-analysis - Jue-Rong Feng; Fan Wang; Xiao Qiu; Lynne V. McFarland; Peng-Fei Chen; Rui Zhou; Jing Liu; Qiu Zhao; Jin Li (European Journal of Clinical Pharmacology, 2017)

Efficient Generation of Functionally Active Spinal Cord Neurons from Spermatogonial Stem Cells - Hao Yang; Cuicui Liu; Bo Chen; Jing An; Rui Zhang; Qian Zhang; Jingjing Zhao; Baorong He; Ding-Jun Hao (Molecular Neurobiology, 2017)

Increasing the recovery of heavy metal ions using two microbial fuel cells operating in parallel with no power output - Xiaohui Wang; Jing Li; Zhao Wang; Hairti Tursun; Rui Liu; Yanmei Gao; Yuan Li (Environmental Science and Pollution Research, 2016)

Quantitative determination constraints on dolomitization model for the Upper Permian Changxing reservoir dolomites of Northeastern Sichuan Basin, Southwestern China - Rui Zhao; Ya Sheng Wu; Hong Xia Jiang; Qing Song Liu; Li Jing Liu (Carbonates and Evaporites, 2016)

Lead Exposure Impairs Hippocampus Related Learning and Memory by Altering Synaptic Plasticity and Morphology During Juvenile Period - Tao Wang; Rui-Li Guan; Ming-Chao Liu; Xue-Feng Shen; Jing Yuan Chen; Ming-Gao Zhao; Wen-Jing Luo (Molecular Neurobiology, 2016)

Evaluation of a water-soluble adjuvant for the development of monoclonal antibodies against small-molecule compounds - Rui Liu; Ying Liu; Mei-jing Lan; Niusha Taheri; Jing-li Cheng; Yi-rong Guo; Guo-nian Zhu (Journal of Zhejiang University-SCIENCE B, 2016)

Role of CSL-dependent and independent Notch signaling pathways in cell apoptosis - Chong Zeng; Rui Xing; Jing Liu; Feiyue Xing (Apoptosis, 2016)

Pectin Modifications: A Review - Jun Chen; Wei Liu; Cheng-Mei Liu; Ti Li; Rui-Hong Liang; Shun-Jing Luo (Critical Reviews in Food Science and Nutrition, 2015)

Anti-inflammatory effect of procyanidin B1 on LPS-treated THP1 cells via interaction with the TLR4–MD-2 heterodimer and p38 MAPK and NF-κB signaling - Jing Xing; Rui Li; Nan Li; Jian Zhang; Yueqing Li; Ping Gong; Dongna Gao; Hui Liu; Yu Zhang (Molecular and Cellular Biochemistry, 2015)

Baicalein inhibits prostate cancer cell growth and metastasis via the caveolin-1/AKT/mTOR pathway - Zhaoxin Guo; Xiaolin Hu; Zhaoquan Xing; Rui Xing; Renguang Lv; Xiangyu Cheng; Jing Su; Zunlin Zhou; Zhonghua Xu; Sten Nilsson; Zhaoxu Liu (Molecular and Cellular Biochemistry, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

Integrated SWAT model and statistical downscaling for estimating streamflow response to climate change in the Lake Dianchi watershed, China - Jing Zhou; Dan He; Yufeng Xie; Yong Liu; Yonghui Yang; Hu Sheng; Huaicheng Guo; Lei Zhao; Rui Zou (Stochastic Environmental Research and Risk Assessment, 2015)

Molecular Cloning and Functional Analysis of an Ethylene Receptor Gene from Sugarcane (Saccharum spp.) by Hormone and Environmental Stresses - Ai-Qin Wang; Xing-Zhi Ye; Jing-Li Huang; Jun-Qi Niu; Ming Liu; Yong-Bao Pan; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Transcription of the Human Sodium Channel SCN1A Gene Is Repressed by a Scaffolding Protein RACK1 - Zhao-Fei Dong; Ling-Jia Tang; Guang-Fei Deng; Tao Zeng; Shu-Jing Liu; Rui-Ping Wan; Ting Liu; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2014)

Origin of sanukitoid and hornblendite enclaves in the Dajitu pluton from the Yinshan Block, North China Craton: product of Neoarchaean ridge subduction? - Xudong Ma; Hong-Rui Fan; M. Santosh; Xuan Liu; Jing-Hui Guo (International Geology Review, 2014)

A novel variant in the 3′ UTR of human SCN1A gene from a patient with Dravet syndrome decreases mRNA stability mediated by GAPDH’s binding - Tao Zeng; Zhao-Fei Dong; Shu-Jing Liu; Rui-Ping Wan; Ling-Jia Tang; Ting Liu; Qi-Hua Zhao; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Human Genetics, 2014)

Zircon geochronology constraints on the age and nature of ‘Precambrian metamorphic rocks’ in the Xing’an block of Northeast China - Wei Sun; Xiao-Guo Chi; Zhi Zhao; Shi-Yu Pan; Jian-Feng Liu; Rui Zhang; Jing-Yu Quan (International Geology Review, 2014)

Effects of bromide and iodide ions on the formation of disinfection by-products during ozonation and subsequent chlorination of water containing biological source matters - Xiao-song Zha; Yan Liu; Xiang Liu; Qiang Zhang; Rui-hua Dai; Ling-wen Ying; Jin Wu; Jing-ting Wang; Luming Ma (Environmental Science and Pollution Research, 2014)

Effect of sulphate nutrition on arsenic translocation and photosynthesis of rice seedlings - Rui Song; Chen-Yun Zhao; Juan Liu; Jing Zhang; Yan-Xiu Du; Jun-Zhou Li; Hong-Zheng Sun; Hong-Bing Zhao; Quan-Zhi Zhao (Acta Physiologiae Plantarum, 2013)

CTLA-4 polymorphisms and systemic lupus erythematosus (SLE): a meta-analysis - Jin-Xia Zhai; Li-Wei Zou; Zhao-Xiang Zhang; Wen-Jing Fan; Han-Yong Wang; Ting Liu; Zheng Ren; Rui-Xue Dai; Dongqing Ye (Molecular Biology Reports, 2013)

Molecular Cloning and Expression Analysis of Nine ThTrx Genes in Tamarix hispida - Li Hui-yu; Ning Kun; Song Xin; Wang Zi-jia; Liu Gui-feng; Jiang Jing; Zhang Rui-ping; Li Kai-long (Plant Molecular Biology Reporter, 2013)

Effects of Ethephon on Key Enzymes of Sucrose Metabolism in Relation to Sucrose Accumulation in Sugarcane - Ai-Qin Wang; Wen-Jing Huang; Jun-Qi Niu; Ming Liu; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2013)

A miR-570 binding site polymorphism in the B7-H1 gene is associated with the risk of gastric adenocarcinoma - Weipeng Wang; Fang Li; Yong Mao; Huan Zhou; Jing Sun; Rui Li; Cuiping Liu; Weichang Chen; Dong Hua; Xueguang Zhang (Human Genetics, 2013)

Erratum to: Unexpectedly high outcrossing rate in both dense and sparse patches in self-compatible Pedicularis rex (Orobanchaceae) - Jing Xia; Hong Liu; Rui Qin (Plant Systematics and Evolution, 2013)

Unexpectedly high outcrossing rate in both dense and sparse patches in self-compatible Pedicularis rex (Orobanchaceae) - Xia Jing; Liu Hong; Qin Rui (Plant Systematics and Evolution, 2013)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

Effect of yeast polysaccharide on some hematologic parameter and gut morphology in channel catfish (Ictalurus punctatus) - Huiling Zhu; Huiyu Liu; Jing Yan; Rui Wang; Lihe Liu (Fish Physiology and Biochemistry, 2012)

Gastrin inhibits a novel, pathological colon cancer signaling pathway involving EGR1, AE2, and P-ERK - Ling-Jun Song; Rui-Jun Liu; Zhi Zeng; Seth L. Alper; Heng-Jing Cui; Yang Lu; Lin Zheng; Zhao-Wen Yan; Guo-Hui Fu (Journal of Molecular Medicine, 2012)

Evaluation of the Use of SCAR Markers for Screening Genetic Diversity of Lentinula edodes Strains - Jing-Yu Liu; Zheng-He Ying; Fang Liu; Xin-Rui Liu; Bao-Gui Xie (Current Microbiology, 2012)

Production of Chitinase and its Optimization from a Novel Isolate Serratia marcescens XJ-01 - Jin-Lan Xia; Jing Xiong; Rui-Yong Zhang; Ke-Ke Liu; Bin Huang; Zhen-Yuan Nie (Indian Journal of Microbiology, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

MicroRNA-17 post-transcriptionally regulates polycystic kidney disease-2 gene and promotes cell proliferation - Huan Sun; Qing-Wei Li; Xiao-Yan Lv; Jian-Zhong Ai; Qiu-Tan Yang; Jing-Jing Duan; Guo-Hui Bian; Yan Xiao; Yi-Dong Wang; Zheng Zhang; Yu-Hang Liu; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Isolation and Analysis of Rice Rf1-Orthologus PPR Genes Co-segregating with Rf3 in Maize - Xiang-Bo Xu; Zhan-Xian Liu; Deng-Feng Zhang; Ying Liu; Wei-Bin Song; Jian-Sheng Li; Jing-Rui Dai (Plant Molecular Biology Reporter, 2009)

Regulation of skeletal muscle differentiation in fibroblasts by exogenous MyoD gene in vitro and in vivo - Rui-feng Qin; Tian-qiu Mao; Xiao-ming Gu; Kai-jing Hu; Yan-pu Liu; Jin-wu Chen; Xin Nie (Molecular and Cellular Biochemistry, 2007)

Prohibitin suppresses renal interstitial fibroblasts proliferation and phenotypic change induced by transforming growth factor-β1 - Wei Guo; Hong Xu; Jing Chen; Yong Yang; Jia Wei Jin; Rui Fu; Hai Mei Liu; Xi Liang Zha; Zhi Gang Zhang; Wen Yan Huang (Molecular and Cellular Biochemistry, 2007)